Adhesive composition and pressure sensitive adhesive sheet

By using an acidic synthetic rubber emulsion and a rosin-based resin emulsion, combined with a crosslinker and a primer layer, the problem of insufficient strength and residual glue during high and low speed peeling of the adhesive is solved, and environmentally friendly and efficient bonding effect is achieved, and suitable for laser processing and surface protection.

JP2025014436APending Publication Date: 2025-01-30NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023116984
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

The existing water-based adhesive compositions have insufficient adhesive strength during high-speed peeling and low-speed peeling, and residual glue is easily left during the peeling process, which is difficult to meet the needs of laser processing and surface protection, and there is also the problem of insufficient mechanical stability.

Method used

Adhesive compositions containing more than 50% acidic synthetic rubber emulsions and rosin-based resin emulsions are used to combine crosslinking agents and primer layers to improve the bonding strength and reduce residual glue. An environmentally friendly water-based adhesive composition is used to reduce the use of organic solvents.

Benefits of technology

The strength during high-speed peeling and stability during low-speed peeling are achieved, which reduces the residual glue leaving, is suitable for laser processing and surface protection, while reducing the use of organic solvents and improving mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014436000001_ABST
    Figure 2025014436000001_ABST
Patent Text Reader

Abstract

To provide a rubber-based latex-containing adhesive composition excellent in mechanical stability, the adhesive composition capable of forming an adhesive agent having high-speed peeling strength and excellent in adhesive residue prevention properties and adherend pollution prevention properties.SOLUTION: An adhesive composition includes: rubber-based latex including acid-modified synthetic rubber latex of 50 wt.% or more according to a nonvolatile content; and a rosin-based tackifier emulsion as a tackifier. In the adhesive composition, glass-transition temperature of acid-modified synthetic rubber included in the acid-modified synthetic rubber latex is -20°C or lower. A softening point of rosin-based tackifier included in the rosin-based tackifier emulsion is 140°C or lower.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition and a pressure-sensitive adhesive sheet. [Background technology]

[0002] Generally, adhesives (also called pressure-sensitive adhesives; the same applies below) are in a soft solid (viscoelastic) state at temperatures around room temperature and have the property of easily adhering to an adherend by pressure. Taking advantage of such properties, adhesives are widely used in various fields for purposes such as joining, fixing, surface protection, masking, and marking, for example in the form of an adhesive sheet having an adhesive layer on a substrate. For example, Patent Document 1 is a technical document relating to an adhesive sheet that can be used for surface protection during laser processing. Patent Document 2 is a technical document relating to an aqueous adhesive composition containing a rubber latex and a tackifier resin emulsion. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 7058096 [Patent Document 2] Patent No. 4676945 Summary of the Invention [Problem to be solved by the invention]

[0004] The adhesive sheet may be required to have various characteristics depending on the purpose and the scene of use. For example, in an application where the adhesive sheet is attached to an adherend and then exposed to a high-speed peel load, the adhesive sheet is required to have a peel strength (high-speed peel strength) that does not cause lifting or peeling from the adherend against such a high-speed peel load. An example of an application requiring such high-speed peel strength is a laser processing application. Laser processing is a technique for processing various materials, such as cutting and drilling, using a carbon dioxide gas laser with a dominant wavelength of about 9.3 μm to 10.6 μm or a short-wavelength laser with a dominant wavelength of about 0.9 μm to 1.1 μm. As an embodiment of laser processing, an adhesive sheet as an auxiliary material is attached to an object to be processed (a workpiece, hereinafter also referred to as a "work"), which is an adherend, and the workpiece is laser-processed together with the adhesive sheet by irradiating the adhesive sheet with laser light. The adhesive sheet that can be used in such an embodiment preferably has a high-speed peel strength suitable for suppressing lifting or peeling caused by an assist gas supplied during laser processing.

[0005] In particular, by using a short-wavelength laser beam with a main wavelength of about 0.9 μm to 1.1 μm, the energy required for processing can be efficiently applied to the workpiece. This can be advantageous in terms of speeding up processing and fine processing. On the other hand, in processing with a short-wavelength laser, the assist gas pressure tends to be high in order to speed up processing. For this reason, it is particularly desirable that the adhesive sheet expected to be used in processing with a short-wavelength laser has a certain level of high-speed peel strength in order to prevent the occurrence of an event in which such a high-pressure assist gas gets between the workpiece and the workpiece and the workpiece is lifted off.

[0006] The adhesive sheet may also be required to have a resistance to peeling under a low-speed peel load, i.e., a predetermined low-speed peel strength. For example, the workpiece cut or otherwise processed by the laser light may then be subjected to post-processing such as bending or drilling. In this case, the adhesive sheet attached as an auxiliary material for laser processing is used for the post-processing in a state where it is still attached to the workpiece after the laser processing. At this time, if the low-speed peel strength of the adhesive sheet is too low, there is a concern that the adhesive sheet will not be able to withstand bending, pulling, etc. in the post-processing, and peeling will occur. For this reason, it is desirable for the adhesive sheet used in laser processing to have a low-speed peel strength of a certain level or more in order to suppress the occurrence of peeling in the post-processing.

[0007] On the other hand, a pressure-sensitive adhesive sheet used for surface protection of an adherend is attached to the surface of the adherend, and after achieving its protective purpose, it is usually peeled off (re-peeled off) from the adherend. Therefore, the pressure-sensitive adhesive sheet used for such purposes must have a peel strength against the adherend limited to a range that allows re-peeling. In addition, when re-peeling from the adherend, it is desirable that there is no problem (glue residue) in that adhesive residue remains on the adherend surface, and that the adherend is peeled off without contaminating it. It is also desirable that a pressure-sensitive adhesive sheet used for surface protection during laser processing does not leave any glue residue or contaminate when peeled off after processing including laser processing.

[0008] In recent years, there has been a demand for a reduction in the amount of organic solvents used from the viewpoint of environmental consideration and reduction in the use of petroleum resources. From this viewpoint, for example, for rubber-based adhesives, it is more desirable to use an aqueous adhesive composition containing a rubber latex than a solvent-based adhesive composition in which the adhesive component is dissolved in an organic solvent. However, adhesive compositions containing natural rubber latex tend to be insufficient in stability (mechanical stability) against mechanical shear (shear force) of the adhesive composition. When the mechanical stability of the adhesive composition is insufficient, aggregates are likely to be generated by the mechanical shear applied during the delivery by a gear pump or coating by a roll coater. The generation of such aggregates can be a factor that reduces the commercial value (for example, appearance quality) of an adhesive sheet manufactured using the adhesive composition.

[0009] The mechanical stability of the natural rubber latex-containing adhesive composition can be improved by using a protective colloid, an emulsifier, or a dispersant, as proposed in, for example, Patent Document 2. However, such additives can have a negative effect on the adhesive properties. For example, the inclusion of an additive such as an emulsifier can cause a decrease in peel strength, such as high-speed peel strength. In addition, the adhesive containing the above additives tends to have a decreased anchoring property to a substrate such as a resin film, and there is a risk of adhesive residue being generated when the adhesive sheet is removed from the adherend. In particular, an adhesive formed from a rubber-based latex-containing adhesive composition is likely to have insufficient anchoring property to a polyolefin-based resin film substrate. The anchoring property to the substrate can be improved by providing an undercoat layer on the substrate, but sufficient adhesive residue prevention may not be obtained even then. Furthermore, additives such as emulsifiers contained in the adhesive can bleed out and cause contamination of the adherend surface.

[0010] The present invention has been made in view of the above circumstances, and aims to provide a pressure-sensitive adhesive composition containing a rubber-based latex that has good mechanical stability, has good high-speed peel strength, and is capable of forming a pressure-sensitive adhesive that is excellent in preventing adhesive residue and preventing contamination of an adherend. Another related aim is to provide a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition. [Means for solving the problem]

[0011] According to this specification, a pressure-sensitive adhesive composition is provided that contains a rubber-based latex containing 50% by weight or more of acid-modified synthetic rubber latex based on non-volatile content, and a rosin-based tackifier emulsion as a tackifier. In this pressure-sensitive adhesive composition, the glass transition temperature of the acid-modified synthetic rubber contained in the acid-modified synthetic rubber latex is -20°C or lower. In addition, the softening point of the rosin-based tackifier contained in the rosin-based tackifier emulsion is 140°C or lower. According to the pressure-sensitive adhesive composition having the above configuration, good mechanical stability is obtained with a composition using rubber latex. In addition, it is possible to form a pressure-sensitive adhesive that has good high-speed peel strength and is less likely to leave adhesive residue or stain on the adherend surface during peeling. That is, it is possible to achieve both good high-speed peel strength and excellent adhesive residue prevention and adherend stain prevention. The pressure-sensitive adhesive composition can be obtained from a rubber-based latex and a rosin-based tackifier emulsion without relying on organic solvents. Therefore, it is possible to substantially not use organic solvents or to reduce the amount of organic solvent used. This is significant in terms of eliminating organic solvents and being environmentally friendly.

[0012] In some preferred embodiments, the pressure-sensitive adhesive composition contains an acid-modified styrene-butadiene copolymer latex as the acid-modified synthetic rubber latex. The technology disclosed herein is preferably carried out in an embodiment using an acid-modified styrene-butadiene copolymer latex.

[0013] In some preferred embodiments, the content of the tackifier is 50 parts by weight or more and 100 parts by weight or less based on the non-volatile content of the rubber latex. By setting the content of the tackifier within the above range, it is possible to preferably realize excellent prevention of adhesive transfer and prevention of contamination of the adherend while having good high-speed peel strength.

[0014] In some embodiments, the pressure-sensitive adhesive composition does not contain a crosslinking agent, or contains the crosslinking agent in an amount of 5 parts by weight or less per 100 parts by weight of the rubber latex, based on the non-volatile content. By setting the content of the crosslinking agent within the above range, the resulting pressure-sensitive adhesive layer has good high-speed peel strength and suitable cohesive force, and is likely to exhibit excellent resistance to adhesive transfer and contamination of the adherend.

[0015] The specification also provides a pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer made of any of the pressure-sensitive adhesive compositions disclosed herein and a substrate supporting the pressure-sensitive adhesive layer. A pressure-sensitive adhesive sheet comprising a substrate and a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition disclosed herein has good high-speed peel strength due to the pressure-sensitive adhesive layer formed with good mechanical stability, and is less likely to leave adhesive residue or stain the adherend surface upon peeling.

[0016] In some embodiments, the pressure-sensitive adhesive sheet has an undercoat layer disposed between the substrate and the pressure-sensitive adhesive layer. By disposing the undercoat layer between the substrate and the pressure-sensitive adhesive layer, the anchoring property of the pressure-sensitive adhesive layer can be increased, and the resistance to adhesive transfer can be improved. In this specification, "anchoring property" refers to the resistance of the adhesive layer to peeling from the substrate, regardless of whether the substrate and the adhesive layer are in direct contact with each other, in other words, the resistance to destruction (anchor destruction) between the adhesive layer and the substrate. Therefore, in this specification, "anchoring property of the adhesive layer to the substrate" or an equivalent expression is used not only for the anchoring property of the adhesive layer to the substrate in a configuration in which the substrate and the adhesive layer are in contact with each other, but also for a configuration in which an undercoat layer is present between the substrate and the adhesive layer.

[0017] In some embodiments, the pressure-sensitive adhesive sheet comprises a polyolefin-based resin film as the substrate.The pressure-sensitive adhesive sheet comprising a polyolefin-based resin film substrate is suitable for applications in which the sheet is cut by laser light, specifically laser processing applications, because the cutting width is easily controlled and the cut end surface is easily formed with good shape accuracy when cut by laser light, for example.In addition, for example, the anchoring property of the aqueous pressure-sensitive adhesive composition is generally low with respect to the polyolefin-based resin film substrate, but by providing an undercoat layer on the surface of the polyolefin-based resin film substrate, the anchoring property of the pressure-sensitive adhesive layer can be increased and the adhesive residue prevention property can be improved.

[0018] In some preferred embodiments, the undercoat layer contains a polymer having an oxazoline group. By using an oxazoline group-containing polymer as the undercoat layer material, the anchoring power of the pressure-sensitive adhesive layer formed by containing a rubber-based latex is improved, and more excellent adhesive transfer prevention properties are easily obtained.

[0019] The pressure-sensitive adhesive sheet disclosed herein is unlikely to leave adhesive residue or stain when peeled off from an adherend, and is therefore suitable as a pressure-sensitive adhesive sheet for surface protection that is attached to the surface of an adherend, achieves its protective purpose, and is peeled off from the adherend.

[0020] The adhesive sheet disclosed herein has a good high-speed peel strength, so even if it is attached to an object to be processed (adherend) and cut together with the object to be processed with a laser beam, it is unlikely to be lifted or peeled off from the adherend due to assist gas pressure. Therefore, the adhesive sheet disclosed herein can be preferably used as an adhesive sheet for laser processing that is cut with a laser beam (e.g., a carbon dioxide gas laser, a short-wavelength laser, or the like). The adhesive sheet is particularly suitable as an adhesive sheet for laser processing that is cut with a short-wavelength laser beam (hereinafter, also referred to as a "specific laser beam") having a main wavelength in the range of 900 nm to 1100 nm. A suitable example of the laser processing application is an application for protecting the surface of a metal plate during laser processing of the metal plate. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic diagram of a pressure-sensitive adhesive sheet according to an embodiment. [Diagram 2] FIG. 4 is a cross-sectional view illustrating a schematic diagram of a pressure-sensitive adhesive sheet according to another embodiment. [Diagram 3] FIG. 4 is a cross-sectional view illustrating a schematic diagram of a pressure-sensitive adhesive sheet according to another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] A preferred embodiment of the present invention will be described below. Matters other than those specifically mentioned in this specification that are necessary for carrying out the present invention can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general knowledge in the field. In addition, in the following drawings, members and parts that perform the same function may be described by using the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments described in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the pressure-sensitive adhesive sheet of the present invention that is actually provided as a product.

[0023] The concept of adhesive sheet here may include those called adhesive tape, adhesive label, adhesive film, etc. The above-mentioned adhesive layer is typically formed continuously, but is not limited to such a form, and may be an adhesive layer formed in a regular or random pattern such as a dotted or striped pattern. The adhesive sheet disclosed herein may be in the form of a roll or a sheet. Alternatively, it may be cut or punched into an appropriate shape depending on the application or mode of use.

[0024] In addition, in this specification, the term "adhesive" refers to a material that exhibits a soft solid (viscoelastic) state in a temperature range around room temperature and has the property of easily adhering to an adherend by pressure, as described above. The adhesive referred to here is generally a material having a complex tensile modulus E * (1Hz)<10 7 dyne / cm 2 The material may be a material having the above properties at 25° C.

[0025] <Adhesive composition> (Rubber Latex (A)) The adhesive composition disclosed herein contains a rubber-based latex (A). The rubber-based latex (A) contains 50% by weight or more of acid-modified synthetic rubber latex based on the non-volatile content. The glass transition temperature (Tg) of the acid-modified synthetic rubber contained in the acid-modified synthetic rubber latex is -20°C or lower. The rubber-based latex refers to a dispersion in which a rubber-based polymer such as an acid-modified synthetic rubber is dispersed in water, and the acid-modified synthetic rubber latex refers to a dispersion in which an acid-modified synthetic rubber is dispersed in water. By using an acid-modified synthetic rubber latex as the rubber-based latex (A), it is easier to obtain good mechanical stability compared to a composition using natural rubber latex. In addition, in an embodiment in which an adhesive layer is formed on a substrate, the action of acid modification can improve anchoring properties to the substrate or the undercoat layer on the substrate. In addition, due to the improvement in cohesive strength and anchoring properties of the adhesive based on the acid modification, adhesive residue is less likely to be left on the adherend surface when peeled off. For example, a pressure-sensitive adhesive formed using an acid-modified synthetic rubber latex is more likely to provide anchoring properties to resin films and the like than a pressure-sensitive adhesive formed using natural rubber latex or synthetic rubber that is not acid-modified. In addition, by using an acid-modified synthetic rubber with a Tg of -20°C or less, adhesion to adherends such as metal materials can be improved, and high-speed peel strength in particular can be improved. In addition, other additive components such as tackifiers are easily compatible, and contamination of the adherend surface tends to be suppressed.

[0026] In some preferred embodiments, from the viewpoint of improving mechanical stability and anchoring property, the ratio of the acid-modified synthetic rubber latex in the rubber-based latex (A) is about 60% by weight or more, more preferably about 70% by weight or more, even more preferably about 80% by weight or more, even more preferably about 90% by weight or more, and even more preferably about 95% by weight or more, based on the non-volatile content. It is particularly preferable that the rubber-based latex (A) is substantially composed of the acid-modified synthetic rubber latex. For example, additives such as emulsifiers that may be contained in natural rubber latex may bleed out and cause contamination of the adherend surface, so increasing the ratio of the acid-modified synthetic rubber latex is also advantageous in terms of preventing contamination of the adherend. In some other embodiments, from the viewpoint of effectively obtaining the effect of blending a rubber-based polymer other than the acid-modified synthetic rubber latex (specifically, natural rubber, non-acid-modified synthetic rubber), the proportion of the acid-modified synthetic rubber latex contained in the rubber-based latex (A) may be about 90% by weight or less, about 80% by weight or less, or 70% by weight or less based on the non-volatile content.

[0027] In this specification, "X is substantially composed of Y" means that the ratio of Y in X is 97% by weight or more and 100% by weight or less, and preferably 99% by weight or more and 100% by weight or less, and does not exclude the unintentional inclusion of components other than Y in X.

[0028] In some preferred embodiments, the Tg of the acid-modified synthetic rubber contained in the acid-modified synthetic rubber latex is about -30°C or less, more preferably about -40°C or less, and even more preferably about -50°C or less, from the viewpoint of improving high-speed peel strength and reducing contamination of the adherend surface. In some embodiments, the lower limit of the Tg of the acid-modified synthetic rubber is, for example, about -80°C or more, may be about -70°C or more, or may be about -65°C or more. For the Tg of the acid-modified synthetic rubber, the manufacturer's nominal value may be used for commercially available products. When the manufacturer's nominal value is unknown or the synthetic rubber obtained by synthesis is analyzed with a differential scanning calorimeter (DSC), the Tg of the synthetic rubber can be confirmed from the temperature of the inflection point of the obtained calorific curve. As the DSC, the product name "Q2000" manufactured by TA Instruments or an equivalent product can be used.

[0029] As the acid-modified synthetic rubber latex, for example, an acid-modified synthetic rubber latex obtained by acid-modifying various synthetic rubber latexes such as styrene-butadiene copolymer latex (SBR latex), nitrile rubber latex (NBR latex), and chloroprene latex is used. Among them, it is preferable to use an acid-modified SBR latex as the acid-modified synthetic rubber latex. As the acid-modified synthetic rubber latex, a synthetic rubber latex that has been acid-modified by a known or conventional method may be used. For example, the synthetic rubber in the latex may be modified with an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, or fumaric acid, or an anhydride of the unsaturated carboxylic acid, to obtain an acid-modified synthetic rubber latex. Alternatively, a commercially available product may be obtained as the acid-modified synthetic rubber latex. The acid-modified synthetic rubber may be used alone or in combination of two or more.

[0030] The presence or absence of acid modification of synthetic rubber latex can be confirmed by forming a film of the synthetic rubber latex and analyzing it by the ATR method (attenuated total reflection method) using FT-IR. As an analysis device, for example, "Nicolet iS10" manufactured by Thermo Fisher Scientific Inc. or an equivalent product can be used.

[0031] In some embodiments, the rubber latex (A) may or may not contain a rubber polymer other than the acid-modified synthetic rubber latex (for example, natural rubber latex, synthetic rubber not modified with acid). Examples of other rubber latexes containing such rubber polymers include natural rubber latex and synthetic rubber latex not modified with acid. The other rubber latexes can be used alone or in combination of two or more. For example, by using a predetermined amount of natural rubber latex as the other rubber latex, the peel strength can be improved. In addition, in a use mode in which an adhesive sheet is attached to a processing object (adherend) and the processing object is subjected to laser processing, by using natural rubber as an adhesive component, it is easy to obtain an adhesive that can suppress lifting or peeling of the adhesive sheet due to assist gas pressure even if the time until the processing is performed is shortened. Note that natural rubber latex refers to a dispersion liquid in which natural rubber is dispersed in water.

[0032] The natural rubber contained in the natural rubber latex may be, for example, depolymerized or not depolymerized. The natural rubber may be unmodified natural rubber latex or modified natural rubber latex modified with, for example, an acrylic acid ester. Unmodified natural rubber latex and modified natural rubber latex may be used in combination. As the natural rubber latex, a non-deproteinized natural rubber latex that has not been subjected to deproteinization treatment is usually used, but a deproteinized natural rubber latex that has been subjected to deproteinization treatment may also be used. The deproteinization treatment may be carried out by various known methods, such as a method of treating with a protease. The natural rubber may be used alone or in combination of two or more kinds.

[0033] In some embodiments, unmodified natural rubber latex is used as the natural rubber latex from the viewpoints of adhesion, productivity, etc. In such embodiments, the proportion of unmodified natural rubber latex contained in the natural rubber latex is about 50% by weight or more (e.g., more than 50% by weight) based on the non-volatile content, may be about 70% by weight or more, may be about 90% by weight or more, or may be about 95% by weight or more, and the natural rubber contained in the natural rubber latex may be substantially composed of unmodified natural rubber.

[0034] In some embodiments, non-deproteinized natural rubber latex is used as the natural rubber latex. By using non-deproteinized natural rubber latex, high cohesive strength tends to be obtained. In such embodiments, the proportion of non-deproteinized natural rubber latex contained in the natural rubber latex is about 50% by weight or more (e.g., more than 50% by weight) based on the non-volatile content, and may be about 70% by weight or more, about 90% by weight or more, or about 95% by weight or more, and the natural rubber contained in the natural rubber latex may be substantially composed of non-deproteinized natural rubber. Although not particularly limited, the protein mass in the non-deproteinized natural rubber is about 0.2 to 0.7% by weight in terms of nitrogen content.

[0035] (Tackifier (B)) The pressure-sensitive adhesive composition contains a rosin-based tackifier emulsion as a tackifier (B). The softening point of the rosin-based tackifier contained in the rosin-based tackifier emulsion is 140°C or less. The rosin-based tackifier emulsion refers to a dispersion in which a rosin ester as a tackifier is dispersed in water. An emulsion containing a rosin-based tackifier having a softening point of 140°C or less is well compatible with the acid-modified synthetic rubber latex, and can improve the adhesiveness of the pressure-sensitive adhesive layer with less contamination of the adherend. The rosin-based tackifier emulsion can be used alone or in combination of two or more.

[0036] Examples of the rosin-based tackifier include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc.) obtained by modifying the unmodified rosin through hydrogenation, disproportionation, polymerization, etc.; and various other rosin derivatives. Examples of the rosin derivatives include rosin esters and rosin phenols. Examples of the rosin esters include rosin esters obtained by esterifying unmodified or modified rosin with a polyhydric alcohol; polyhydric alcohol esters of unsaturated fatty acid-modified rosin obtained by partially modifying unmodified or modified rosin with an unsaturated fatty acid (fumaric acid, maleic acid, etc.) and then esterifying it; and polyhydric alcohol esters of unsaturated fatty acid-modified disproportionated rosin obtained by partially modifying unmodified or modified rosin with an unsaturated fatty acid, then disproportionating it, and then esterifying it. Examples of the rosin phenols include those obtained by adding phenols to rosins and thermally polymerizing the resulting phenols; those obtained by esterifying the thermally polymerized products; and the like. The polyhydric alcohol used in the esterification is not particularly limited, and various known polyhydric alcohols such as diethylene glycol, glycerin, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, 1,2,4-butanetriol, and pentaerythritol can be used. Among these, rosin esters are preferably used as the rosin tackifier. The rosin tackifiers can be used alone or in combination of two or more.

[0037] In some preferred embodiments, from the viewpoints of improving compatibility and high-speed peel strength, the rosin-based tackifier used has a softening point of about 130° C. or less. The softening point of the rosin-based tackifier is more preferably about 120° C. or less, even more preferably about 110° C. or less, even more preferably about 100° C. or less, and particularly preferably about 90° C. or less. From the viewpoints of preventing adhesive residue and adherend contamination, the softening point of the rosin-based tackifier is preferably about 60° C. or more, more preferably about 70° C. or more, even more preferably about 80° C. or more, and may be about 90° C. or more.

[0038] In this specification, the softening point of the tackifier is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is melted as quickly as possible at a low temperature and then filled into a ring placed on a flat metal plate, taking care not to create bubbles. After cooling, the part that protrudes from the flat surface including the top end of the ring is cut off with a slightly heated knife. Next, a holder (ring stand) is placed in a glass container (heating bath) with a diameter of 85 mm or more and a height of 127 mm or more, and glycerin is poured in until it is 90 mm or more deep. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and the ring filled with the sample are immersed in glycerin without touching each other, and the temperature of the glycerin is kept at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring and placed in a fixed position on the holder. Next, keeping the distance from the top of the ring to the glycerin surface at 50 mm, place a thermometer and align the center of the thermometer's mercury bulb to the same height as the center of the ring, then heat the container. The flame of the Bunsen burner used for heating should be midway between the center of the bottom of the container and its edge, and heating should be uniform. After heating begins and the temperature of the bath reaches 40°C, the rate of increase must be 5.0 ± 0.5°C per minute. The sample gradually softens and flows down the ring, and the temperature is read when it finally touches the bottom plate, and this is the softening point. The softening point is measured for two or more samples at the same time, and the average value is used.

[0039] The adhesive composition may or may not contain a tackifier other than a rosin-based tackifier having a softening point of 140° C. or less, as long as the effect of the technology disclosed herein is not impaired. Examples of such other tackifiers include rosin-based tackifiers having a softening point higher than 140° C., petroleum-based tackifiers (e.g., aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic / aromatic hydrocarbon resins, hydrogenated versions of these, etc.), terpene-based resins, ketone-based resins, xylene-based resins, etc. The above other tackifiers may be used alone or in combination of two or more.

[0040] In some embodiments, the proportion of the rosin-based tackifier having a softening point of 140° C. or less in the total amount of the tackifier (B) contained in the pressure-sensitive adhesive composition may be about 50% by weight or more, preferably about 70% by weight or more, more preferably about 80% by weight or more, even more preferably about 90% by weight or more, and particularly preferably about 95% by weight or more. It is particularly preferable that the tackifier (B) contained in the pressure-sensitive adhesive composition is substantially composed of a rosin-based tackifier having a softening point of 140° C. or less.

[0041] The rosin-based tackifier emulsion and other tackifier emulsions that can be used as the tackifier (B) can be prepared by appropriately employing a known tackifier resin emulsification method, or a commercially available tackifier emulsion can be used. Examples of the emulsification method include a high-pressure emulsification method and an inversion emulsification method. The high-pressure emulsification method can be carried out, for example, by adding water and a suitable emulsifier to a solution obtained by dissolving a tackifier in a solvent (typically benzene, toluene, etc.), emulsifying using a high-pressure emulsifier, and then removing the solvent (for example, by distilling off under reduced pressure) as necessary. Alternatively, a tackifier emulsion can be prepared without substantially using an organic solvent by heating a tackifier to a temperature above its softening point to make it in a molten state, mixing this with water and a suitable emulsifier, and emulsifying using a high-pressure emulsifier (solvent-free high-pressure emulsification method). The inversion emulsification method can be carried out, for example, by mixing a small amount of a solvent (benzene, toluene, etc.) with a tackifier, kneading in an appropriate emulsifier, and gradually adding hot water to cause phase inversion emulsification to form an emulsion. Alternatively, a tackifier emulsion can be prepared without substantially using an organic solvent by raising the temperature of the tackifier to or above its softening point, kneading in an emulsifier, and gradually adding hot water to cause phase inversion emulsification (solvent-free phase inversion emulsification method).

[0042] The emulsifier used for emulsifying the tackifier is not particularly limited, and may be appropriately selected from known emulsifiers. For example, anionic emulsifiers and nonionic emulsifiers may be used. Examples of anionic emulsifiers include alkyl sulfate type anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfate type anionic emulsifiers such as sodium polyoxyethylene lauryl ether sulfate; polyoxyethylene alkyl phenyl ether sulfate type anionic emulsifiers such as ammonium polyoxyethylene lauryl phenyl ether sulfate and sodium polyoxyethylene lauryl phenyl ether sulfate; sulfonate type anionic emulsifiers such as sodium dodecylbenzenesulfonate; sulfosuccinic acid type anionic emulsifiers such as disodium lauryl sulfosuccinate and disodium polyoxyethylene lauryl sulfosuccinate; and the like. Examples of nonionic emulsifiers include polyoxyethylene alkyl ether type nonionic emulsifiers such as polyoxyethylene lauryl ether; polyoxyethylene alkyl phenyl ether type nonionic emulsifiers such as polyoxyethylene lauryl phenyl ether; polyoxyethylene fatty acid esters, polyoxyethylene polyoxypropylene block polymers, etc. In some embodiments, a salt of rosin may be used as the emulsifier. For example, from the viewpoint of ease of emulsification and stability over time of the emulsion, an ammonium salt of rosin containing 50% by weight or more of dihydroabietic acid is preferably used.

[0043] Although not particularly limited, it is preferable that the emulsification of the tackifier is carried out using the above emulsifier in the presence of a protective colloid such as a water-soluble salt of casein. The water-soluble salt of casein is not particularly limited, and is used in the form of an aqueous casein solution in which casein is dissolved in an aqueous solution of a basic compound (sodium hydroxide, potassium hydroxide, ammonia, organic amines, etc.). For example, an aqueous ammonium casein solution is preferably used.

[0044] The content of the tackifier (B) (preferably a rosin-based tackifier having a softening point of 140° C. or less; the same applies below) in the pressure-sensitive adhesive composition is not particularly limited, and may be an appropriate amount that provides the desired high-speed peel strength, adhesive residue prevention, and adherend contamination prevention. In some embodiments, the content of the tackifier (B) relative to 100 parts by weight of the rubber-based latex (A) may be more than 30 parts by weight, for example, approximately 40 parts by weight or more, based on the non-volatile content. By using a predetermined amount or more of the tackifier (B) (preferably a rosin-based tackifier having a softening point of 140° C. or less), a good high-speed peel strength is easily obtained, and the low-speed peel strength can also be adjusted to a desired range. From the viewpoint of obtaining high adhesiveness, in some preferred embodiments, the content of the tackifier (B) relative to 100 parts by weight of the rubber latex (A) is about 50 parts by weight or more, more preferably about 55 parts by weight or more, even more preferably about 60 parts by weight or more, even more preferably about 65 parts by weight or more, particularly preferably about 70 parts by weight or more, and may be about 80 parts by weight or more, or may be about 90 parts by weight or more. In some embodiments, the content of the tackifier (B) relative to 100 parts by weight of the rubber latex (A) may be about 150 parts by weight or less, about 130 parts by weight or less, about 120 parts by weight or less, or about 110 parts by weight or less, based on the non-volatile content. By appropriately limiting the content of the tackifier (B) within the above range, the tackifier (B) is easily compatible with the rubber-based latex (A) and good adhesive properties (e.g., high-speed peel strength) are easily obtained. In addition, it can be easily peeled off from the adherend. In some preferred embodiments, the content of the tackifier (B) relative to 100 parts by weight of the rubber-based latex (A) is about 100 parts by weight or less, may be about 95 parts by weight or less, may be about 90 parts by weight or less, may be about 85 parts by weight or less, may be about 80 parts by weight or less, or may be about 75 parts by weight or less, based on the non-volatile content. By setting the content of the tackifier (B) within the above range, it is possible to improve the peelability from the adherend while maintaining sufficient adhesiveness. For example, the cohesive strength of the adhesive layer is suppressed from decreasing, and there is a tendency for the adhesive layer to have excellent adhesive residue prevention and adherend contamination prevention after peeling the adhesive from the adherend.

[0045] In some embodiments, the adhesive composition may be such that the total amount of the rubber latex (A) and the tackifier (B) accounts for 70% by weight or more of the total weight of the adhesive composition based on the non-volatile content (i.e., the weight of the adhesive layer constituted by this adhesive). This allows the effects of containing the components (A) and (B) to be preferably exhibited. In some preferred embodiments, the total amount of the components (A) and (B) may be 80% by weight or more, 90% by weight or more (e.g., 90 to 100% by weight), or 95% by weight or more (e.g., 95 to 100% by weight) of the total weight of the adhesive composition based on the non-volatile content. The adhesive composition having the above composition allows the effects of the technology disclosed herein to be preferably realized.

[0046] (Crosslinking agent (C)) The adhesive composition may or may not contain a crosslinking agent (C). In some embodiments, the adhesive composition preferably contains a crosslinking agent (C). The use of the crosslinking agent (C) can improve anchoring properties. In an embodiment in which the above-mentioned adhesive composition is applied to an adhesive sheet having a substrate, the inclusion of a crosslinking agent makes it easier to obtain good anchoring properties for the substrate or the undercoat layer on the substrate. In addition, the use of a crosslinking agent makes it possible for the resulting adhesive layer to have a moderate cohesive force and to suppress the occurrence of adhesive residue. It is believed that such an effect is obtained by a good reaction between the acid in the acid-modified synthetic rubber latex and the crosslinkable reactive group of the crosslinking agent. Note that the technology disclosed herein is not limited to the above interpretation. As the crosslinking agent (C), an aqueous crosslinking agent is preferably used. The use of an aqueous crosslinking agent is also meaningful in terms of eliminating organic solvents and being environmentally friendly. Note that the concept of an aqueous crosslinking agent includes water-dispersible crosslinking agents and water-soluble crosslinking agents.

[0047] As the crosslinking agent (C), an isocyanate-based crosslinking agent, an oxazoline-based crosslinking agent, an epoxy-based crosslinking agent, an aziridine-based crosslinking agent, a carbodiimide-based crosslinking agent, a metal chelate-based crosslinking agent, etc. can be used. The crosslinking agent (C) can be used alone or in combination of two or more. Among them, it is preferable to use an aqueous crosslinking agent having at least one functional group selected from an oxazoline group, an isocyanate group, and an epoxy group as the crosslinking agent (C). In other words, an oxazoline-based crosslinking agent, an isocyanate-based crosslinking agent, or an epoxy-based crosslinking agent can be preferably used as the crosslinking agent (C). By blending an aqueous crosslinking agent having the specific functional group described above into the adhesive composition containing the rubber latex (A), the anchoring property to a substrate such as a resin film can be improved. Although not particularly limited, an oxazoline-based crosslinking agent, an isocyanate-based crosslinking agent, or an epoxy-based crosslinking agent can adhere well to an undercoat layer containing a polymer having an oxazoline group, for example, and can exhibit excellent anchoring property.

[0048] Examples of isocyanate crosslinking agents include polyfunctional isocyanate compounds having two or more functionalities. Examples of isocyanate crosslinking agents include aromatic isocyanates such as tolylene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatophenyl)thiophosphate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate. As the isocyanate crosslinking agent, either water-soluble or water-dispersible isocyanate crosslinking agents may be used. As the isocyanate crosslinking agent, a so-called blocked isocyanate type isocyanate crosslinking agent in which the isocyanate group is blocked may be used. Examples of commercially available products include the "Burnoc DNW" series manufactured by DIC Corporation, the "Aquanate" series manufactured by Tosoh Corporation, the "Takenate WD" series manufactured by Mitsui Chemicals, Inc., and the "Elastron BN" series manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0049] As the oxazoline crosslinking agent, a compound having one or more oxazoline groups in one molecule can be used. The oxazoline group may be any of 2-oxazoline group, 3-oxazoline group, and 4-oxazoline group. An oxazoline crosslinking agent having a 2-oxazoline group can be preferably used. For example, a water-soluble copolymer or a water-dispersed copolymer obtained by copolymerizing an addition polymerizable oxazoline such as 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline with another monomer can be used as the oxazoline crosslinking agent. As the oxazoline crosslinking agent, either water-soluble or water-dispersed type can be used, but a water-soluble oxazoline crosslinking agent is preferably used. Commercially available oxazoline-based crosslinking agents include, for example, products manufactured by Nippon Shokubai Co., Ltd. under the trade names "Epocross WS-500," "Epocross WS-700," "Epocross K-2010E," "Epocross K-2020E," and "Epocross K-2035E."

[0050] As the epoxy crosslinking agent, a compound having two or more epoxy groups in one molecule can be used. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. As the epoxy crosslinking agent, either water-soluble or water-dispersible type can be used, but a water-soluble epoxy crosslinking agent is preferably used. Specific examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, (poly)ethylene glycol diglycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available epoxy crosslinking agents include those available under the trade name "Epicron CR-5L" manufactured by DIC Corporation, and those available under the trade names "Denacol EX-313," "Denacol EX-512," "Denacol EX-810," "Denacol EX-821," "Denacol EX-830," and "Denacol EX-850" manufactured by Nagase ChemteX Corporation.

[0051] Examples of the aziridine crosslinking agent include trimethylolpropane tris[3-(1-aziridinyl)propionate], trimethylolpropane tris[3-(1-(2-methyl)aziridinylpropionate)], etc. Examples of commercially available aziridine crosslinking agents include trade names "ChemiTite PZ-33" and "ChemiTite DZ-22E" manufactured by Nippon Shokubai Co., Ltd.

[0052] As the carbodiimide crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used. Commercially available products of the carbodiimide crosslinking agent include, for example, the Carbodilite V series (aqueous solution type) such as "Carbodilite V-02", "Carbodilite V-02-L2", and "Carbodilite V-04" manufactured by Nisshinbo Corporation, and the Carbodilite E series (aqueous dispersion type) such as "Carbodilite E-01", "Carbodilite E-02", and "Carbodilite E-04".

[0053] In some preferred embodiments, at least one selected from an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent is used as the crosslinking agent (C). Compared with, for example, an isocyanate-based crosslinking agent, an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent have good stability in the adhesive composition and are advantageous in terms of productivity. In addition, an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent are likely to provide excellent adhesive transfer prevention properties. In an embodiment in which the adhesive composition is applied to an adhesive sheet having a substrate, the presence of an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent can improve the anchoring properties of the adhesive layer to the substrate or the undercoat layer. From this viewpoint, in some embodiments, the total proportion of the oxazoline-based crosslinking agent and the epoxy-based crosslinking agent in the total amount of the crosslinking agent (C) contained in the adhesive composition may be about 10% by weight or more, about 30% by weight or more, or about 50% by weight or more based on the non-volatile content. In some preferred embodiments, the total amount of the oxazoline-based crosslinking agent and the epoxy-based crosslinking agent in the total amount of the crosslinking agent (C) is more than 50% by weight, more preferably about 70% by weight or more, even more preferably about 90% by weight or more, and particularly preferably about 95% by weight or more, based on the non-volatile content. The crosslinking agent (C) may be substantially composed of at least one selected from the oxazoline-based crosslinking agent and the epoxy-based crosslinking agent.

[0054] In some embodiments, it is particularly preferable to use an oxazoline-based crosslinking agent as the crosslinking agent (C). The oxazoline-based crosslinking agent can react at a relatively low heating temperature of about 80° C., so that the desired adhesive properties are developed early, and the adhesive properties have good stability over time. It is also suitable when the heating temperature is limited during the preparation of the adhesive sheet, such as when a polyolefin-based resin film is used. In addition, the oxazoline-based crosslinking agent is also advantageous in that the degree of crosslinking can be efficiently increased by using a relatively small amount. Furthermore, the adhesive layer formed using the oxazoline-based crosslinking agent tends to have good processability. From this viewpoint, in some embodiments, the ratio of the oxazoline-based crosslinking agent to the total amount of the crosslinking agent (C) contained in the adhesive composition may be about 10% by weight or more, about 30% by weight or more, or about 50% by weight or more based on the non-volatile content. In some preferred embodiments, the proportion of the oxazoline-based crosslinking agent in the total amount of the crosslinking agent (C) is more than 50% by weight, more preferably about 70% by weight or more, even more preferably about 90% by weight or more, and particularly preferably about 95% by weight or more, based on the non-volatile content. The crosslinking agent (C) may be substantially composed of the oxazoline-based crosslinking agent.

[0055] In some embodiments, it is preferable that the crosslinking agent (C) does not contain an isocyanate-based crosslinking agent or that the amount of the isocyanate-based crosslinking agent used is limited. This can suppress the short pot life and gelation during storage caused by the inclusion of a relatively highly active isocyanate-based crosslinking agent, and can improve productivity. From this viewpoint, in some embodiments, the proportion of the isocyanate-based crosslinking agent in the total amount of the crosslinking agent (C) contained in the pressure-sensitive adhesive composition may be approximately 50% by weight or less (for example, less than 50% by weight), approximately 30% by weight or less, approximately 10% by weight or less, approximately 3% by weight or less, or approximately 1% by weight or less. The crosslinking agent (C) may not substantially contain an isocyanate-based crosslinking agent.

[0056] In an embodiment in which the pressure-sensitive adhesive composition contains a crosslinking agent (C), the content of the crosslinking agent (C) in the pressure-sensitive adhesive composition is not particularly limited, and may be an appropriate amount that can achieve both high-speed peel strength, adhesive residue prevention, and adherend contamination prevention. In some embodiments, the content of the crosslinking agent (C) in the pressure-sensitive adhesive composition may be about 0.01 parts by weight or more per 100 parts by weight of the rubber latex (A) based on the non-volatile content. In some preferred embodiments, the content of the crosslinking agent (C) is about 0.1 parts by weight or more per 100 parts by weight of the rubber latex (A) based on the non-volatile content, more preferably about 0.3 parts by weight or more, even more preferably about 0.5 parts by weight or more, even more preferably 0.8 parts by weight or more, particularly preferably 1.0 parts by weight or more, and may be about 2.0 parts by weight or more, 3.0 parts by weight or more, or 4.0 parts by weight or more. By blending a predetermined amount or more of the crosslinking agent (C), the resulting pressure-sensitive adhesive layer has suitable cohesive strength and anchoring properties, and is easy to obtain excellent adhesive residue prevention and adherend contamination prevention. In some embodiments, the content of the crosslinking agent (C) may be about 8 parts by weight or less, or about 6 parts by weight or less, based on the non-volatile content, per 100 parts by weight of the rubber latex (A). By appropriately limiting the amount of the crosslinking agent (C) used, the peel strength can be adjusted to a preferred range, and good high-speed peel strength is easy to obtain. In addition, contamination of the adherend surface after removal of the pressure-sensitive adhesive is easy to prevent. From the viewpoint of achieving a better balance between high-speed peel strength, adhesive residue prevention, and adherend contamination prevention, in some preferred embodiments, the content of the crosslinking agent (C) relative to 100 parts by weight of the rubber latex (A) is approximately 5.0 parts by weight or less, more preferably approximately 4.0 parts by weight or less, even more preferably approximately 3.5 parts by weight or less, even more preferably approximately 3.0 parts by weight or less, even more preferably approximately 2.5 parts by weight or less, particularly preferably approximately 2.0 parts by weight or less, and may be approximately 1.5 parts by weight or less, based on the non-volatile content.In addition, in an embodiment in which the pressure-sensitive adhesive composition does not contain a crosslinking agent (C) or the amount of the crosslinking agent (C) is limited, the content of the crosslinking agent (C) relative to 100 parts by weight of the rubber latex (A) based on the non-volatile content can be less than 1.0 part by weight, for example, less than 0.3 part by weight or less than 0.1 part by weight, and the pressure-sensitive adhesive composition may be substantially free of the crosslinking agent (C).

[0057] (Laser light absorber) The adhesive composition may contain a laser beam absorbent as necessary, or may not contain the laser beam absorbent. By containing a laser beam absorbent in the adhesive composition, the adhesive layer formed from the adhesive composition can be a laser beam absorbing layer, and the cutting property by laser beam can be improved. As the laser beam absorbent that can be contained in the adhesive composition, one or more types can be appropriately selected from the laser beam absorbents exemplified below. In an embodiment in which the adhesive composition contains a laser beam absorbent, the content of the laser beam absorbent in the adhesive composition is usually 5% by weight or less on a non-volatile basis, and from the viewpoint of adhesive performance, it is preferably 3% by weight or less, and may be 1% by weight or less. Alternatively, the technology disclosed herein can be preferably implemented in an embodiment in which the adhesive composition, and in turn the adhesive layer formed from the adhesive composition, does not substantially contain a laser beam absorbent.

[0058] (Anti-aging agent) The adhesive composition may contain an antioxidant as necessary. The quality stability of the adhesive may be improved by using an antioxidant. The antioxidant may be used alone or in combination of two or more. Examples of the antioxidant include phosphorus-based antioxidants, phenol-based antioxidants, hindered amine-based antioxidants, aromatic amine-based antioxidants, and sulfur-based antioxidants. Although not particularly limited, the amount of the antioxidant contained in the adhesive composition may be, for example, approximately 20 parts by weight or less, and usually 10 parts by weight or less is appropriate, and may be 5 parts by weight or less, based on the non-volatile content, based on 100 parts by weight of the rubber-based latex (A). In addition, the amount of the antioxidant may be, for example, 0.1 parts by weight or more, may be 0.5 parts by weight or more, or may be 1 part by weight or more, based on the non-volatile content, based on 100 parts by weight of the rubber-based latex (A).

[0059] (optional ingredient) The adhesive composition may contain various additives that can be used in the field of adhesive compositions (typically, water-dispersed adhesive compositions), such as viscosity adjusters (thickeners, etc.), leveling agents, dispersants, plasticizers, softeners, fillers, colorants such as pigments and dyes, light stabilizers, antioxidants, water-resistant agents, defoamers, preservatives, and crosslinking assistants, as necessary. The dispersant is preferably one that can function as a protective colloid, and examples of the dispersant that can be used include water-soluble polymers such as gelatin, polyvinyl alcohol, polyvinyl alcohol derivatives, water-soluble salts of cellulose, cellulose derivatives, and polyacrylic acid (salts) that do not have hydrophobic side chains. The adhesive composition may also contain an emulsifier as necessary. Examples of such emulsifiers that can be used include those exemplified as emulsifiers that can be used for emulsifying tackifier emulsions.

[0060] In some embodiments, the adhesive composition may be a composition in which the total amount of the rubber latex (A), the tackifier (B), and the crosslinking agent (C) accounts for 70% by weight or more of the total weight of the adhesive composition based on the non-volatile content (i.e., the weight of the adhesive layer constituted by this adhesive). This allows the effects of containing the above-mentioned (A), (B), and (C) components to be suitably exhibited. In some preferred embodiments, the total amount of the above-mentioned (A), (B), and (C) components may be 80% by weight or more, 90% by weight or more (e.g., 90 to 100% by weight), or 95% by weight or more (e.g., 95 to 100% by weight) of the total weight of the adhesive composition based on the non-volatile content. The adhesive composition having the above composition allows the effects of the technology disclosed herein to be suitably realized.

[0061] (Water-dispersible pressure-sensitive adhesive composition) The adhesive composition disclosed herein can be prepared using an aqueous component as described above, so that organic solvents are not substantially used or the amount of organic solvent used can be reduced. This is significant in terms of organic solvent removal and environmental consideration. The adhesive composition can typically be implemented in the form of an aqueous dispersion type adhesive composition containing an acid-modified synthetic rubber latex and a rosin-based tackifier emulsion. In this specification, the aqueous dispersion type adhesive composition refers to a composition in which at least a part of the adhesive-forming components is dispersed in water. The aqueous dispersion type also includes a suspended state and an emulsified state. Therefore, the concept of the aqueous dispersion type adhesive composition includes what is called an emulsion type adhesive composition. The aqueous dispersion type adhesive composition contains water as a dispersion medium or solvent. The aqueous dispersion type adhesive composition may contain a liquid other than water as necessary. The liquid other than water may be, for example, one or more selected from various organic solvents (such as lower alcohols) that can be uniformly mixed with water. Generally, the proportion of water in the volatile components contained in the water-dispersed pressure-sensitive adhesive composition is, for example, 90% by weight or more, and preferably 95 to 100% by weight.

[0062] In some embodiments, from the viewpoint of environmental consideration and the absence of organic solvents, it is preferable that the PSA composition (typically, a water-dispersed PSA composition) is substantially free of organic solvents. Here, the PSA composition being substantially free of organic solvents means that the amount of organic solvent in the PSA composition is less than 1 wt % (e.g., less than 0.1 wt %).

[0063] <Adhesive> According to this specification, a pressure-sensitive adhesive formed from the pressure-sensitive adhesive composition disclosed herein is provided. The pressure-sensitive adhesive may be a pressure-sensitive adhesive obtained by curing the pressure-sensitive adhesive composition by drying, crosslinking, cooling, or the like, i.e., a cured product of the pressure-sensitive adhesive composition. The curing means for the pressure-sensitive adhesive composition (e.g., drying, crosslinking, cooling, etc.) may be a single operation of each curing means, or a plurality of operations may be applied simultaneously or in multiple stages. In this specification, a pressure-sensitive adhesive formed from a water-dispersed pressure-sensitive adhesive composition is also referred to as a water-dispersed pressure-sensitive adhesive.

[0064] <Adhesive sheet> (Configuration example) According to this specification, there is provided a pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from any of the pressure-sensitive adhesive compositions disclosed herein. The pressure-sensitive adhesive sheet may be a substrate-attached pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer on one or both sides of a sheet-like substrate (support), or may be a substrate-less pressure-sensitive adhesive sheet (i.e., a pressure-sensitive adhesive sheet without a non-releasable substrate) having the pressure-sensitive adhesive layer provided on a release liner.

[0065] The structure of the adhesive sheet according to one embodiment is shown in FIG. 1. The adhesive sheet 1 includes a substrate 10, an undercoat layer 30 provided on a first surface 10A of the substrate 10, and an adhesive layer 20 disposed on the surface 30A of the undercoat layer 30, and is used by attaching the adhesive layer 20 to an adherend. The undercoat layer 30 is in contact with the adhesive layer 20. In the adhesive sheet 1, the other surface (back surface, second surface) 10B of the substrate 10 is a surface (release surface) having releasability. The adhesive sheet 1 before use (i.e., before attachment to an adherend) may be in the form of a roll 50 in which the surface (adhesive surface) 20A of the adhesive layer 20 is wound around a core (roll core) 52 in a roll shape so that the surface 20A of the adhesive layer 20 abuts against the back surface 10B of the substrate 10, as shown in FIG. 1, for example, and thus the surface 20A is protected. The adhesive sheet 1 may also be in the form of a roll without a core 52, that is, a so-called coreless type roll in which the adhesive sheet 1 is wound alone. Alternatively, the adhesive sheet 1 before use may be in the form of a roll, or may be in the form of a laminate in which the adhesive layer surface of one adhesive sheet is abutted against the back surface of another adhesive sheet to form a laminate in which the adhesive surface 20A is protected. Alternatively, the surface 20A of the adhesive sheet 1 before use may be protected by a release liner, rather than by the back surface of the substrate constituting the adhesive sheet.

[0066] The adhesive sheet may have a cross-sectional structure as shown in FIG. 2. In the adhesive sheet 2 shown in FIG. 2, the substrate 10 includes a back layer 11 constituting the other surface (second surface) 10B of the substrate 10, and a support layer 12 disposed on the inside of the back layer 11 (the side on which the adhesive layer 20 is provided). In this embodiment, the substrate 10 is made of a resin film. The back layer 11 is made of a resin composition containing a release agent, and the surface of the back layer 11 (which also serves as the second surface 10B of the substrate 10) is a release surface. The support layer 12 may be a layer made of a resin composition that does not contain a release agent, or may be a layer made of a resin composition that contains a release agent. In the adhesive sheet 2 shown in FIG. 2, the substrate 10 has a two-layer structure consisting of the back layer 11 and the support layer 12, but the structure of the substrate 10 is not limited to a two-layer structure.

[0067] The adhesive sheet 3 shown in Fig. 3 is a modified example of the adhesive sheet 2 shown in Fig. 2, and differs from the adhesive sheet 2 in that it does not have an undercoat layer. Specifically, the adhesive sheet 3 comprises a substrate 10 and an adhesive layer 20 provided on one surface (first surface) 10A of the substrate 10. The substrate 10 includes a back layer 11 constituting the other surface (second surface) 10B of the substrate 10, and a support layer 12 arranged on the inner side of the back layer 11 (the side on which the adhesive layer 20 is provided). In the configuration shown in Fig. 3, from the viewpoint of the anchoring property of the adhesive layer 20 to the substrate 10, it is preferable that the support layer 12 is a layer made of a resin composition that does not contain a release agent.

[0068] (Adhesive layer) The pressure-sensitive adhesive layer can be formed, for example, by applying (typically applying) any of the pressure-sensitive adhesive compositions disclosed herein to a substrate, an undercoat layer provided on the substrate, or a release liner, and drying the composition. The pressure-sensitive adhesive composition can be applied using a known or conventional coater, such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, or a spray coater. From the viewpoint of promoting the crosslinking reaction, improving the production efficiency, etc., it is preferable to dry the pressure-sensitive adhesive composition under heating. For example, a drying temperature of about 40 to 120°C, about 40 to 100°C, or about 40 to 80°C can be adopted. After drying the pressure-sensitive adhesive composition, aging may be performed, for example, within a range of room temperature or higher and about 60°C or lower, for the purpose of adjusting the component migration in the pressure-sensitive adhesive layer, advancing the crosslinking reaction, and relaxing distortion that may exist in the pressure-sensitive adhesive sheet. In the case of a substrate-attached pressure-sensitive adhesive sheet, the pressure-sensitive adhesive layer may be formed by applying the pressure-sensitive adhesive composition directly to the substrate, or the pressure-sensitive adhesive layer formed on a release liner may be transferred to the substrate.

[0069] The thickness of the adhesive layer can be appropriately set so that appropriate adhesive performance is obtained depending on the application of the adhesive sheet. The thickness of the adhesive layer is usually appropriate to be about 0.5 μm to 200 μm. From the viewpoint of improving adhesion to the adherend, in some preferred embodiments, the thickness of the adhesive layer may be, for example, 1.5 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, or 10 μm or more. In addition, the thickness of the adhesive layer may be, for example, about 150 μm or less, or about 100 μm or less. By limiting the thickness of the adhesive layer, the adhesive sheet can be made thinner. In addition, limiting the thickness of the adhesive layer is also preferable in terms of preventing the occurrence of adhesive residue due to cohesive failure of the adhesive layer. In some preferred embodiments, the thickness of the adhesive layer is about 50 μm or less, 30 μm or less, 20 μm or less, 18 μm or less, 16 μm or less, or 15 μm or less. The above-mentioned small thickness of the adhesive layer can be advantageous, for example, in terms of the speed and precision of laser processing in an adhesive sheet that can be used in a manner in which it is laser cut together with an adherend (workpiece).

[0070] (base material) In some embodiments, the pressure-sensitive adhesive sheet may be in the form of a substrate-attached pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer on one or both sides of a substrate (support substrate). A pressure-sensitive adhesive sheet having a substrate can improve productivity, handling, processability, etc. In addition, a pressure-sensitive adhesive sheet having a substrate can have good removability from an adherend. The material of the substrate is not particularly limited, and can be appropriately selected depending on the purpose and mode of use of the pressure-sensitive adhesive sheet. Non-limiting examples of substrate materials that can be used include various resin films, foam sheets, woven and nonwoven fabrics made of various fibrous substances alone or in a blend, papers, metal foils, etc. Substrates having a composite configuration of these may also be used.

[0071] In some embodiments, the pressure-sensitive adhesive sheet includes a resin film as a substrate. Here, the term "resin film" refers to a resin film that has a non-porous structure and typically does not substantially contain air bubbles (void-free). Therefore, the resin film is a concept that is distinguished from foam films and nonwoven fabrics. Examples of resin materials that constitute the resin film include, but are not limited to, polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); polyolefin resins such as polyethylene, polypropylene, ethylene-propylene copolymers, and polypropylene-polyethylene blend resins; and vinyl chloride resins (typically soft vinyl chloride resins), vinyl acetate resins, and polyamide resins.

[0072] In some embodiments, from the viewpoint of various processability due to the flexibility of the substrate, or from the viewpoint of cuttability and non-contamination of the adhesive sheet by a specific laser beam, for example, polyolefin-based resin film or polyester-based resin film can be preferably used as the resin film. Among them, polyolefin-based resin film is preferable from the viewpoint of conformability to the adherend. Generally, the anchoring property of the aqueous adhesive composition tends to decrease with respect to the polyolefin-based resin film substrate, but according to the technology disclosed herein, by using a polyolefin-based resin film substrate, it is possible to obtain good anchoring property and thus adhesive transfer prevention property while enjoying the advantages of the polyolefin-based resin film.

[0073] Here, the polyolefin resin film refers to a resin film whose main component is a polyolefin resin. In this specification, the main component refers to a component contained in an amount of more than 50% by weight, unless otherwise specified. For example, when the main component of a resin film is a polyolefin resin, the resin film contains a polyolefin resin in an amount of more than 50% by weight of its total weight. A suitable example of a polyolefin resin film is a resin film whose main component is a polyethylene (PE) resin and / or a polypropylene (PP) resin. A polyolefin resin film contains a PE resin and / or a PP resin, and the total amount of the PE resin and the PP resin may be more than 50% by weight of the polyolefin resin film, preferably 70% by weight or more, for example 85% by weight or more. The above total amount corresponds to the content of the PE resin in a resin film containing a PE resin and not a PP resin.

[0074] The PE resin may be mainly composed of various polymers (ethylene-based polymers) having ethylene as the main constituent monomer unit. The PE resin may be substantially composed of one or more ethylene-based polymers. The ethylene-based polymer may be a homopolymer of ethylene, or may be a copolymer of ethylene as the main monomer with another α-olefin as a secondary monomer (random copolymerization, block copolymerization, etc.). Suitable examples of the α-olefin include α-olefins having 3 to 10 carbon atoms, such as propylene, 1-butene (which may be branched 1-butene), 1-hexene, 4-methyl-1-pentene, and 1-octene. For example, a PE resin mainly composed of an ethylene-based polymer copolymerized with the α-olefin as a secondary monomer at a ratio of 10% by weight or less (typically 5% by weight or less) may be preferably used.

[0075] The PE resin may also be a PE resin containing a copolymer of ethylene and a monomer (functional group-containing monomer) having another functional group in addition to the polymerizable functional group, or a PE resin in which such a functional group-containing monomer is copolymerized with an ethylene-based polymer, etc. Examples of copolymers of ethylene and functional group-containing monomers include ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl methacrylate copolymer (EMMA), and ethylene-(meth)acrylic acid (i.e., acrylic acid and / or methacrylic acid) copolymers crosslinked with metal ions.

[0076] The density of the PE resin is not particularly limited. The concept of PE resin here includes high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE) and linear low density polyethylene (LLDPE). In some embodiments, the density of the PE resin is, for example, 0.90 to 0.94 g / cm. 3 Preferred PE resins include LDPE and LLDPE.

[0077] The PP resin may be a polymer (propylene-based polymer) having propylene as the main constituent monomer unit, i.e., a polymer having more than 50% by weight of all constituent monomer units being propylene as the main component. The PP resin may be substantially composed of one or more propylene-based polymers. The concept of propylene-based polymer here includes homopolypropylene, as well as random copolymers (random polypropylenes) and block copolymers (block polypropylenes) of propylene and other monomers.

[0078] The first surface of the substrate (i.e., the surface on which the adhesive layer is provided) may be subjected to an appropriate surface treatment to enhance adhesion to the adhesive layer or the undercoat layer, as necessary. Examples of surface treatments to enhance adhesion include corona discharge treatment, acid treatment, ultraviolet irradiation treatment, plasma treatment, etc.

[0079] In some preferred embodiments, the second surface of the substrate is a release surface, which typically means that an adhesive sheet having a surface (adhesive surface) of an adhesive layer provided on the first surface of the substrate in contact with the release surface can be peeled off without leaving any adhesive residue (residual adhesive) on the release surface.

[0080] In some embodiments, the resin composition constituting the second surface (hereinafter also referred to as "second surface forming material") preferably contains a release agent. A substrate having such a second surface can be understood as a substrate having the release agent kneaded into at least the second surface. The second surface forming material needs only to constitute at least the second surface of the substrate, and may, for example, constitute only the second surface side of the substrate, or may constitute the entire substrate.

[0081] The second surface forming material can be preferably a resin composition containing at least a release agent and a resin material. The resin material can be, but is not limited to, various materials exemplified as the resin material constituting the resin film as the substrate, such as polyester resins such as PET and PBT; polyolefin resins such as PE, PP, ethylene-propylene copolymer, and PP-PE blend resin; and other vinyl chloride resins (typically soft vinyl chloride resins), vinyl acetate resins, and polyamide resins.

[0082] Examples of release agents that can be used as a component of the second surface forming material (i.e., release agents for kneading into the second surface) include ethylene-vinyl alcohol copolymers, fatty acid amide additives, low molecular weight polyolefin waxes, long chain alkyl additives, silicone release agents, etc. The release agents can be used alone or in appropriate combination of two or more. It is preferable to select a release agent that has good mixability with the resin component contained in the second surface forming material.

[0083] As the ethylene-vinyl alcohol copolymer, for example, an ethylene-vinyl alcohol copolymer obtained by saponifying a copolymer of ethylene with vinyl acetate, vinyl formate, vinyl propionate, or vinyl acetate can be used. Examples of fatty acid amide additives include saturated fatty acid bisamides, unsaturated fatty acid bisamides, aromatic bisamides, and substituted ureas. More specifically, examples of fatty acid amide additives include methylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bisoleic acid amide, N,N-dioleyl adipic acid amide, N-stearyl-N'-stearyl urea, and other N-stearyl-N'-stearyl acid amides. These fatty acid amide additives may be used alone or in combination of two or more. As the low molecular weight polyolefin wax, for example, low molecular weight waxes such as polyethylene wax and polypropylene wax can be appropriately used. As the long-chain alkyl additive, low molecular weight additives having an alkyl chain, such as Peloil (registered trademark) 1010 and Peloil (registered trademark) 1010S (both manufactured by Ipposha Yushi Kogyo Co., Ltd.), can be appropriately used. Examples of silicone-based release agents include silylated polyolefins, silicone resins, silicone alkoxy oligomers, silicone oligomers, silicone master pellets, silicone rubber powders, silicone emulsions, etc. As the silylated polyolefins, for example, silylated polyolefins prepared by the method shown in the examples of JP-A-2011-26448 can be used.

[0084] Suitable examples of the release agent for kneading on the second surface include the above-mentioned long-chain alkyl additives and silicone-based release agents. Among them, silicone-based release agents are particularly preferred. As the silicone-based release agent, silylated polyolefin is particularly preferred.

[0085] The content of the release agent in the second-surface forming material is not particularly limited, and may be, for example, about 0.01 to 80% by weight of the entire second-surface forming material. In some embodiments, the content of the release agent in the second-surface forming material may be, for example, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 0.7% by weight or more, or 1% by weight or more. From the viewpoint of compatibility with the resin material, etc., the content of the release agent in the second-surface forming material may be, for example, 70% by weight or less, 50% by weight or less, 30% by weight or less, or 10% by weight or less.

[0086] The substrate may have a single layer structure or a multi-layer structure of two or more layers. In some embodiments, a substrate with a multi-layer structure may be preferably used. A substrate with a multi-layer structure has an advantage that the function and appearance of the first surface and the second surface of the substrate can be easily made different. In a substrate with a multi-layer structure, the types of materials (e.g., resin materials) constituting each layer may be the same or different. The substrate with a multi-layer structure may have, for example, a 2-layer to 5-layer structure, or may have a 2-layer or 3-layer structure. In some other embodiments, the substrate may have a single layer structure. A substrate with a single layer structure may be advantageous in terms of the productivity and quality stability of the substrate.

[0087] The method of forming the substrate (e.g., a resin film substrate) is not particularly limited, and a conventionally known extrusion molding method, such as an inflation extrusion molding method or a cast molding method, can be appropriately adopted. The substrate may be unstretched or may be stretched uniaxially or biaxially. A substrate having a multilayer structure can be obtained by simultaneously molding resin compositions corresponding to each layer (e.g., by a multilayer inflation molding method), laminating each layer after molding, casting another layer on a layer previously molded, or the like, either alone or in combination.

[0088] In some preferred embodiments, the substrate may be a substrate having a multi-layer structure of two or more layers, including a back layer formed from the second surface forming material as described above and a support layer disposed inside the back layer (i.e., on the side closer to the first surface). Hereinafter, the resin composition (i.e., the second surface forming material) forming the back layer in the substrate having such a configuration may be particularly referred to as a "back layer forming material". As with the second surface forming material described above, a resin composition containing a release agent can be preferably used as the back layer forming material. The back layer forming material may be, for example, a resin composition containing at least a release agent and a resin material. The release agent that can be used as a component of the back layer forming material, the content of the release agent in the back layer forming material, and examples of resin materials that can be used as a component of the back layer forming material are the same as those of the second surface forming material described above, so that repeated explanations will be omitted.

[0089] The support layer may be a layer formed from a resin composition. Hereinafter, the resin composition forming the support layer may be referred to as a "support layer forming material". Resin components that can be used as components of the support layer forming material include, but are not limited to, polyester resins, polyolefin resins, vinyl chloride resins, vinyl acetate resins, polyamide resins, etc., similar to the resin materials constituting the above-mentioned resin film. The support layer forming material may contain one type selected from such resin materials alone, or two or more types in appropriate combination. The support layer forming material may not contain a release agent similar to the release agent that can be used in the second surface forming material, or may contain a release agent. In an embodiment in which one surface of the support layer also serves as the first surface of the substrate, it is preferable that the support layer forming material does not contain a release agent from the viewpoint of improving the anchoring property of the pressure-sensitive adhesive layer to the support layer. The resin material constituting the back layer forming material and the resin material constituting the support layer forming material may be the same or different. From the viewpoint of adhesion between the back layer and the support layer, in some embodiments, the resin material constituting the back layer forming material may preferably be the same type of resin as the resin material constituting the support layer forming material.

[0090] The substrate including the back layer and the support layer disposed inside thereof can be obtained, for example, by laminating the support layer forming material and the back layer forming material by co-extrusion molding. The support layer forming material may be co-extrusion molded with the back layer forming material in the form of a preformed base resin film. The number of layers to be laminated in each of the above layers is not particularly limited, and the back layer and the support layer may each be a single layer, or may be a laminate structure of multiple layers as necessary.

[0091] The co-extrusion molding may be a method generally used for the production of films, sheets, etc., and is not particularly limited. Specifically, a multi-layer structure having two, three, or four or more layers may be formed, and for example, an inflation method, a co-extrusion T-die method, etc. may be used. The use of these co-extrusion molding methods is preferable in terms of cost and productivity.

[0092] In the pressure-sensitive adhesive sheet disclosed herein, the method of forming the second surface as a release surface may preferably be a method of forming the second surface of the substrate with a second surface forming material containing a release agent in a resin composition as described above, but is not limited thereto. The second surface of the substrate may be a release surface obtained by, for example, performing a surface treatment in which a release agent is applied to a surface formed from a resin composition that does not contain a release agent. Such a surface treatment may be performed using, for example, a general silicone-based, long-chain alkyl-based, fluorine-based, or other release agent. The surface formed from a resin composition containing a release agent (i.e., the surface into which the release agent is kneaded) may further be subjected to a surface treatment in which a release agent is applied.

[0093] The substrate may contain a laser beam absorbent as necessary. In some embodiments, the laser beam absorbent preferably contains a specific absorbent described below. A suitable example of a substrate containing a laser beam absorbent is a substrate containing a laser beam absorbing layer (which may be a specific absorbent). In a substrate having a multi-layer structure, at least one layer is preferably a laser beam absorbing layer containing a laser beam absorbent. For example, in an embodiment in which the substrate contains a back layer and a support layer, it is preferable that at least one of the back layer and the support layer (for example, both) contains a laser beam absorbent.

[0094] The laser light absorptivity of the substrate including the laser light absorbing layer is not particularly limited, but can be set so that the laser light absorptivity of the adhesive sheet is 20% or more. In some embodiments, the laser light absorptivity of the substrate may be, for example, 15% or more, and usually 20% or more is appropriate, and may be 25% or more, 30% or more, 45% or more, 60% or more, or 75% or more. The laser light absorptivity of the substrate may be 100%, but in practical terms, it is preferably 95% or less, and may be 90% or less. In addition, the transmittance and reflectance of the substrate may be appropriately selected from the same range as the transmittance and reflectance of the adhesive sheet described below.

[0095] The laser beam absorbent contained in the substrate may be one type alone or two or more types in combination selected from the laser beam absorbents exemplified below as usable in the pressure-sensitive adhesive sheet. In an embodiment in which the laser beam absorbent contains a specific absorbent, the specific absorbent may be one type alone or two or more types in combination selected from the laser beam absorbents exemplified below as usable in the pressure-sensitive adhesive sheet. The content of the laser beam absorbent and the content of the specific absorbent in the substrate may be within the ranges exemplified below as the content of the laser beam absorbent and the content of the specific absorbent in the pressure-sensitive adhesive sheet, respectively.

[0096] The substrate may contain any additives as necessary, such as flame retardants, antistatic agents, light stabilizers (radical scavengers, ultraviolet absorbers, etc.), and antioxidants.

[0097] The thickness of the substrate is not particularly limited, and can be, for example, about 5 μm to 300 μm. From the viewpoint of the handleability of the substrate or the adhesive sheet having the substrate, in some preferred embodiments, the thickness of the substrate may be, for example, 15 μm or more, 20 μm or more, 35 μm or more, 50 μm or more, or 75 μm or more. A pressure-sensitive adhesive sheet having a substrate with a predetermined thickness is likely to provide sufficient protection, for example, in the surface protection application of an adherend. In addition, in some preferred embodiments, the thickness of the substrate is, for example, 150 μm or less, 130 μm or less, 110 μm or less, or 90 μm or less. Reducing the thickness of the substrate can be advantageous from the viewpoint of making the adhesive sheet thinner. In addition, when the thickness of the substrate is reduced, the flexibility of the adhesive sheet and its ability to follow the surface shape of the adherend tend to improve. In addition, when applied to laser processing applications, limiting the thickness of the substrate can improve the speed and precision of laser processing. In some other embodiments, the thickness of the substrate can be 70 μm or less, 50 μm or less, or 40 μm or less.

[0098] In a substrate including a back layer (preferably a back layer made of a resin composition containing a release agent) and a support layer, the thickness of the back layer (when the back layer has a laminated structure, the total thickness of those layers) is not particularly limited. From the viewpoint of easily forming a back layer with little thickness unevenness, the thickness of the back layer is advantageously, for example, 1 μm or more, and may be 3 μm or more, or 5 μm or more. The technology disclosed herein can also be suitably implemented in the form of a pressure-sensitive adhesive sheet including a substrate having a back layer with a thickness of more than 7 μm, more than 10 μm, more than 15 μm, more than 20 μm, or more than 25 μm. The upper limit of the thickness of the back layer is not particularly limited, and may be less than the thickness of the entire substrate including the back layer. The thickness of the back layer of the entire substrate thickness can be, for example, 1% or more, 3% or more, 5% or more, or 8% or more, or, for example, 95% or less, 70% or less, 50% or less, 20% or less, or 15% or less. The thickness of the back layer can be, for example, 60 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 10 μm or less, etc., depending on the thickness of the entire substrate. Reducing the thickness of the back layer can be advantageous from the viewpoint of making the pressure-sensitive adhesive sheet thinner.

[0099] From the viewpoints of suppressing unevenness in the thickness of the support layer and handling of the resin film when a preformed resin film is used as the support layer, the thickness of the support layer is usually 5 μm or more, preferably 10 μm or more, may be 25 μm or more, may be 40 μm or more, or may be 60 μm or more. The upper limit of the thickness of the support layer is not particularly limited, and it is sufficient that it is less than the thickness of the entire substrate including the back layer.

[0100] In a substrate including a laser light absorbing layer, the thickness of the laser light absorbing layer (in a substrate including a plurality of laser light absorbing layers, the total thickness of those layers) may be, for example, 3 μm or more, 5 μm or more, or 10 μm or more. From the viewpoint of rapidity and precision of laser processing, in some embodiments, the thickness of the laser light absorbing layer (in other words, the portion where the laser light absorbent is disposed) of the entire thickness of the substrate may be, for example, 20% or more, 50% or more, 70% or more, or 90% or more. Note that, in a substrate including a single layer of a laser light absorbing layer or a substrate including a plurality of laser light absorbent layers, the thickness of the laser light absorbing layer is 100% of the entire thickness of the substrate.

[0101] (Undercoat layer) In some preferred embodiments, the pressure-sensitive adhesive sheet includes an undercoat layer disposed on the surface of the substrate (typically a resin film substrate) on the side of the pressure-sensitive adhesive layer. By disposing the undercoat layer between the substrate and the pressure-sensitive adhesive layer, the anchoring property of the pressure-sensitive adhesive layer can be increased, and the adhesive transfer prevention property can be improved. For example, in an embodiment in which a polyolefin-based resin film is used as the substrate, the anchoring property of the pressure-sensitive adhesive layer can be improved by providing an undercoat layer on the surface of a polyolefin-based resin film substrate in which anchoring property is difficult to obtain. As the undercoat layer forming material (undercoat agent, also called a primer), a known or conventional undercoat agent capable of improving the anchoring power of a rubber-based pressure-sensitive adhesive layer can be used. For example, the undercoat layer may contain one selected from urethane-based resins, polyester-based resins, acrylic-based resins, polyamide-based resins, rubbers such as natural rubber and synthetic rubber, either alone or in combination of two or more resin materials. In addition, an undercoat agent containing an epoxy or isocyanate functional group may be used as the undercoat agent.

[0102] In some preferred embodiments, the undercoat layer is formed from an undercoat agent that contains at least a compound that contains an oxazoline group. The oxazoline group-containing compound is preferably a polymer that contains an oxazoline group, such as an acrylic polymer or a urethane polymer that contains an oxazoline group in its side chain. Among them, the use of an acrylic polymer that has an oxazoline group is particularly preferred. The main chain of the acrylic polymer that has an oxazoline group may be copolymerized with a monomer such as styrene. By including an oxazoline group in the undercoat layer, the anchoring property of the pressure-sensitive adhesive layer that contains an acid-modified synthetic rubber can be effectively improved, and more excellent adhesive transfer prevention properties can be easily obtained.

[0103] In addition, as the undercoat agent, it is preferable to use an aqueous material from the viewpoint of environmental consideration and the elimination of organic solvents. As the aqueous material, either a water-dispersed type (aqueous emulsion) or a water-soluble type can be used. In consideration of the water resistance and performance retention of the undercoat layer, and the influence on the adhesive properties of the adhesive layer provided on the undercoat layer, it is preferable to use an aqueous dispersion type undercoat agent. A suitable example of such an aqueous dispersion type undercoat agent is an oxazoline group-containing polymer emulsion.

[0104] The glass transition temperature (Tg) of the polymer (preferably an oxazoline group-containing polymer) that can be used as an undercoat agent is not particularly limited. In some embodiments, the Tg of the polymer may be about 50°C or less, about 30°C or less, or about 10°C or less. In some preferred embodiments, from the viewpoint of improving the anchoring property of the adhesive layer, the Tg is preferably about 0°C or less, more preferably about -20°C or less, even more preferably about -30°C or less, and even more preferably about -40°C or less. A polymer with a low Tg tends to be easy to apply the undercoat agent to a resin film (e.g., a polyolefin resin film) and has good film-forming properties. In some embodiments, the lower limit of the Tg of the polymer is, for example, about -80°C or more, may be about -70°C or more, or may be about -60°C or more. For the Tg of the polymer, the manufacturer's nominal value may be adopted for commercially available products. When the manufacturer's nominal value is unknown or for polymers obtained by synthesis, analysis can be performed using a differential scanning calorimeter (DSC) to confirm the Tg of the synthetic rubber from the temperature of the inflection point of the obtained heat curve. As a DSC, a TA Instruments product name "Q2000" or an equivalent product can be used.

[0105] Although not particularly limited, in some embodiments, the proportion of the polymer (preferably an oxazoline group-containing polymer) in the undercoat layer is, for example, approximately 50% by weight or more (e.g., more than 50% by weight) based on the non-volatile content, may be approximately 70% by weight or more, may be approximately 90% by weight or more, or may be approximately 95% by weight or more, and the undercoat layer may be substantially composed of the polymer.

[0106] The undercoat agent may contain various additives, such as surfactants, thickeners, stabilizers, defoamers, colorants (pigments, dyes, etc.), etc., as necessary.

[0107] Commercially available undercoat agents used for forming the undercoat layer include those available under the trade names "Epocross K-2010E", "Epocross K-2020E" and "Epocross K-2035E" manufactured by Nippon Shokubai Co., Ltd.

[0108] The undercoat agent can be formed by directly applying the undercoat agent to the surface of the substrate using an applicator such as a wire bar, a spray coater, a fountain die coater, a lip coater, a closed edge die coater, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, etc., and then drying the undercoat agent. The undercoat layer is typically formed continuously, but is not limited thereto, and may be formed in a regular or random pattern such as a dotted or striped pattern.

[0109] The thickness of the undercoat layer (after drying) is not particularly limited. In some embodiments, it may be 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.5 μm or more, or 1.0 μm or more. In some preferred embodiments, the thickness of the undercoat layer is 3 μm or less, 2 μm or less, or 1.5 μm or less. By setting the thickness of the undercoat layer within the above range, the anchoring force improvement effect due to the arrangement of the undercoat layer can be preferably exhibited.

[0110] (Laser Light Absorbing Agent and Laser Light Absorbing Layer) In some preferred embodiments, the adhesive sheet contains a laser beam absorbent. The laser beam absorbent can be used to adjust the laser beam absorptivity of the adhesive sheet. As the laser beam absorbent, various materials that can increase the absorptivity of the laser beam used in processing (typically, at least the absorptivity at the main wavelength) can be preferably used. The type of laser beam absorbent contained in the adhesive sheet may be one type, or two or more types. In an adhesive sheet containing two or more types of laser beam absorbents, the laser beam absorbents may be used in a blend, or may be contained in different layers in the adhesive sheet.

[0111] In this specification, the term "laser beam absorbent" refers to a material that can increase the laser beam absorption rate compared to when the laser beam absorbent is not used. In addition, in this specification, the term "specific absorbing agent" refers to the above-mentioned laser beam absorbents that have as a constituent element a metal with a specific heat of less than 900 J / kg·K and a thermal conductivity of less than 200 W / m·K. In this specification, a layer containing a laser beam absorbent (which may be a specific absorbing agent) may be referred to as a "laser beam absorbing layer."

[0112] Examples of the laser light absorbent that can be used in the adhesive sheet disclosed herein include metals such as aluminum, stainless steel, titanium, nickel, zirconium, tungsten, copper, silver, gold, zinc, molybdenum, chromium, and alloys mainly composed of these metals; metal compounds such as oxides (e.g., titanium oxide, aluminum oxide, etc.), nitrides, and carbides of the above metals; carbon materials such as carbon black and carbon fiber; organic compounds such as phthalocyanine compounds, cyanine compounds, aminium compounds, naphthalocyanine compounds, naphthoquinone compounds, diimonium compounds, anthraquinone compounds, and aromatic dithiol metal complexes (e.g., nickel complexes); and the like. In the laser light absorbing layer containing a laser light absorbent in the resin composition, it is preferable to use a material having a higher thermal decomposition temperature than the resin components constituting the laser light absorbing layer as the laser light absorbent.

[0113] When a powdered laser beam absorbent is used, the shape of the particles constituting the powder is not particularly limited, and may be, for example, flaky, spherical, needle-like, polyhedral, irregular, etc. Usually, a flaky, spherical, or needle-like laser beam absorbent may be preferably used. The average particle size of the laser beam absorbent is not particularly limited, and may be, for example, 0.005 μm or more and 20 μm or less. From the viewpoint of dispersibility, usually, a laser beam absorbent having an average particle size of 10 μm or less or 5 μm or less may be preferably used. From the viewpoint of efficiently increasing the laser beam absorption rate with a small amount of laser beam absorbent, in some embodiments, the average particle size of the laser beam absorbent may be, for example, 3 μm or less, 1 μm or less, 0.6 μm or less, 0.4 μm or less, or 0.3 μm or less. From the viewpoint of powder handling and ease of uniform dispersion, in some embodiments, the average particle size of the laser beam absorbent may be, for example, 0.008 μm or more, 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.15 μm or more, or 0.2 μm or more. In this specification, unless otherwise specified, the term "average particle size" refers to the particle size at an integrated value of 50% in a particle size distribution measured with a particle size distribution measuring device based on a laser scattering / diffraction method (50% volume average particle size).

[0114] In some embodiments, the laser light absorbing layer may contain carbon black as the laser light absorbing agent. For example, carbon black having an average particle size of 10 nm to 500 nm (more preferably 10 nm to 120 nm) may be used. Carbon black may be used alone or in combination with other laser light absorbing agents.

[0115] In some embodiments, the laser light absorbing layer may contain at least one of a metal powder and a metal compound powder as a laser light absorbent. Such a laser light absorbent is preferable because it can withstand heat generation accompanying absorption of a specific laser light and appropriately maintain the property of absorbing the specific laser light. Suitable examples of this type of laser light absorbent include titanium oxide powder, aluminum oxide powder, and metallic aluminum powder.

[0116] The laser light absorbing layer is typically a layer containing a laser light absorbing agent in a resin component. Non-limiting examples of materials that can be used as such a resin component include polyester resins such as PET and PBT; polyolefin resins such as PE, PP, ethylene-propylene copolymers, and PP-PE blend resins; and other vinyl chloride resins, vinyl acetate resins, and polyamide resins. The laser light absorbing layer can be formed by molding a resin composition obtained by blending a laser light absorbing agent with such a resin material into a typically film-like shape.

[0117] When using a laser beam absorbent, its amount is not particularly limited.In some embodiments, the amount of the laser beam absorbent may be, for example, 0.01% by weight or more of the laser beam absorption layer containing the laser beam absorbent, 0.05% by weight or more, or 0.1% by weight or more.In addition, from the viewpoint of reducing laser cutting residue and suppressing reflectance, in some embodiments, the content of the laser beam absorbent may be, for example, 10% by weight or less of the laser beam absorption layer containing the laser beam absorbent, 5% by weight or less, 3% by weight or less, or 2% by weight or less.

[0118] In some embodiments, the pressure-sensitive adhesive sheet disclosed herein may preferably use, as the laser beam absorbent, a specific absorbent, i.e., a laser beam absorbent having as a constituent element a metal with a specific heat of less than 900 J / kg·K and a thermal conductivity of less than 200 W / m·K. The specific absorbent may be selected from the group consisting of any one metal simple substance that satisfies the above specific heat and thermal conductivity; an alloy containing any one metal that satisfies the above specific heat and thermal conductivity at a ratio of more than 50 wt%, more than 70 wt%, or more than 90 wt%; an alloy containing two or more metals that satisfy the above specific heat and thermal conductivity at a ratio of more than 50 wt%, more than 70 wt%, or more than 90 wt% in total; a metal compound containing a metal corresponding to such a simple metal or alloy as a constituent element; and the like. The specific absorbent here includes, for example, iron, iron alloys (for example, iron alloys containing at least one element selected from the group consisting of Cr, Ni, Si, W, Mn, and C), and metal compounds (iron-based compounds) containing a metal (iron-based metal) corresponding to the iron or iron alloy as a constituent element. As the iron-based compound, for example, an oxide of the iron-based metal (iron-based oxide) can be preferably used. Other examples of the specific absorbent include Mn-based compounds containing a metal (Mn-based metal) corresponding to Mn or an Mn alloy as a constituent element, and among them, Mn-based oxides are preferred. The specific absorbent can be used alone or in combination of two or more. In a pressure-sensitive adhesive sheet containing two or more types of specific absorbents, the specific absorbents may be used in a blend, or may be contained in different layers within the pressure-sensitive adhesive sheet.

[0119] In general, the specific heat and thermal conductivity of a metal compound containing a metal as a constituent element tend to be smaller than those of a metal alone. Therefore, in some embodiments of the pressure-sensitive adhesive sheet disclosed herein, a metal compound containing a metal as a constituent element that satisfies the preferred specific heat and thermal conductivity disclosed herein can be preferably used as a specific absorbent. The metal compound that can be used as a specific absorbent can be, for example, an oxide, sulfide, carbide, nitride, hydroxide, oxyhydroxide, etc. of a metal that satisfies the preferred specific heat and thermal conductivity disclosed herein. Other examples of metal compounds that can be used as specific absorbents include metal organic compounds (complexes, etc.) that contain ions of the metal. From the viewpoint of enduring the heat generation accompanying the absorption of specific laser light and appropriately maintaining the property of absorbing the specific laser light, the oxide, sulfide, carbide, and nitride of the above metal are preferred, and oxides are particularly preferred. Examples of the oxides include iron oxide (FeO, Fe3O4, Fe2O3, etc.), manganese dioxide, titanium black, chromium oxide (CrO, Cr2O3, etc.), ferrite, etc., and examples of the sulfides include iron sulfide, molybdenum sulfide, etc., but are not limited to these.

[0120] In the case where the pressure-sensitive adhesive sheet disclosed herein contains a specific absorbent, the content of the specific absorbent is not particularly limited, and may be appropriately selected, for example, from the range of 0.01% by weight or more and 20% by weight or less of the pressure-sensitive adhesive sheet. In some embodiments, the content of the specific absorbent may be, for example, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, or 0.8% by weight or more. When the content of the specific absorbent is high, the absorption rate of the specific laser light tends to be high. On the other hand, when the content of the specific absorbent is too high, the energy of the absorbed specific laser light tends to diffuse in the surface direction, and energy loss may increase. From this viewpoint, the content of the specific absorbent is usually appropriate to be 15% by weight or less of the pressure-sensitive adhesive sheet, preferably 10% by weight or less, more preferably 7% by weight or less, and may be 5% by weight or less or less than 5% by weight.

[0121] The adhesive sheet disclosed herein may contain, in addition to the specific absorbent, a laser light absorbent other than the specific absorbent as needed. Hereinafter, the laser light absorbent other than the specific absorbent used as an auxiliary in this way is also referred to as an "auxiliary absorbent". The auxiliary absorbent may be used for the purpose of, for example, improving the absorption rate of the adhesive sheet, adjusting the transmittance or reflectance, adjusting the appearance, etc. Examples of the auxiliary absorbent include metals such as aluminum, copper, silver, and gold; metal compounds such as oxides, nitrides, and carbides of the above metals; carbon black; organic compounds such as phthalocyanine compounds, cyanine compounds, aminium compounds, naphthalocyanine compounds, naphthoquinone compounds, diimonium compounds, and anthraquinone compounds; and the like.

[0122] The amount of auxiliary absorbent used is preferably less than 50% by weight of the total amount of laser light absorbent contained in the adhesive sheet (i.e., the total amount of the specific absorbent and the auxiliary absorbent), and may be less than 25%, less than 10%, or less than 5%. The adhesive sheet may be substantially free of auxiliary absorbent. Here, substantially free of auxiliary absorbent means that the auxiliary absorbent is not used at least intentionally. The total amount of laser light absorbent contained in the adhesive sheet is suitably 25% by weight or less of the adhesive sheet, and more preferably 20% by weight or less, 15% by weight or less, or 10% by weight or less.

[0123] When the adhesive sheet disclosed herein contains a specific absorbent, the carbon black (CB) content of the adhesive sheet is preferably less than 0.3% by weight of the adhesive sheet, more preferably less than 0.1% by weight, even more preferably less than 0.05% by weight, and particularly preferably 0.02% by weight or less. The reduction in the CB content tends to improve the non-contamination properties of the adhesive sheet. The adhesive sheet may be substantially free of CB, that is, an adhesive sheet in which CB is not used at least intentionally. The adhesive sheet disclosed herein contains a specific absorbent, so that the workpiece can be efficiently processed even if no CB is used or the amount of CB used is limited as described above. With such an adhesive sheet, the improvement in the processing efficiency of the workpiece and the non-contamination properties can be suitably achieved at the same time.

[0124] In some embodiments, a black metal compound may be preferably used as the specific absorbent. The use of a black metal compound can efficiently increase the laser light absorptivity of the adhesive sheet. This makes it possible to preferably realize an adhesive sheet having the above-mentioned preferred laser light absorptivity even if CB is not used or the amount of CB used is limited. The inventors' study has revealed that, unexpectedly, unlike CB, such black metal compounds are less likely to produce black residues. Therefore, the use of a black metal compound can preferably achieve both improved processing efficiency and non-contamination of the workpiece.

[0125] Examples of black metal compounds include, but are not limited to, iron oxide, manganese dioxide, titanium black, chromium oxide, iron sulfide, molybdenum sulfide, etc. In terms of availability, preferred black metal compounds include iron oxide (e.g., FeO, Fe3O4, etc.), titanium black, manganese dioxide, etc. The titanium black is black particles having titanium atoms, and is preferably black particles such as titanium oxynitride and low-order titanium oxide. Among these, preferred black metal compounds include iron oxide and titanium black.

[0126] The content of the black metal compound in the adhesive sheet can be, for example, 0.05% by weight or more of the adhesive sheet, and from the viewpoint of improving the laser light absorption rate, it may be 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, or 0.8% by weight or more. In addition, from the viewpoint of reducing the energy loss due to diffusion in the surface direction of the adhesive sheet, the content of the black metal compound is usually appropriate to be 15% by weight or less of the adhesive sheet, preferably 10% by weight or less, more preferably 7% by weight or less, and may be 5% by weight or less or less than 5% by weight. Alternatively, the proportion of the black metal compound in the specific absorbent may be, for example, more than 50% by weight, may be 70% by weight or more, may be 90% by weight or more, or may be substantially 100% by weight.

[0127] (Adhesive sheet thickness) The thickness of the adhesive sheet is not particularly limited, and is usually about 10 μm to 500 μm. From the viewpoint of the handleability of the adhesive sheet, in some embodiments, the thickness of the adhesive sheet may be, for example, 20 μm or more, 25 μm or more, 40 μm or more, 55 μm or more, 70 μm or more, or 80 μm or more. In some embodiments, the thickness of the adhesive sheet may be, for example, 300 μm or less, 150 μm or less, 120 μm or less, or 100 μm or less. An adhesive sheet having the above thickness can be preferably used for surface protection applications. In addition, when the adhesive sheet is applied to laser processing applications, the speed and precision of the laser processing can be improved by limiting the thickness of the adhesive sheet. In other embodiments, the thickness of the adhesive sheet may be 80 μm or less, 60 μm or less, or 50 μm or less. An adhesive sheet having a reduced thickness as described above can be preferably used for applications in which thinning and weight reduction are desired.

[0128] <Characteristics of adhesive sheet> (High speed peel strength) The adhesive sheet disclosed herein preferably has a high-speed peel strength of 3.0 N / 10 mm or more when it is attached to a stainless steel (SUS) plate and measured at a tensile speed of 30 m / min one week under an environment of 23° C. and 50% RH. The adhesive sheet having the high-speed peel strength is unlikely to lift or peel off from the adherend under high-speed peel load, for example. For example, when the adhesive sheet is used for laser processing, lift or peel off caused by assist gas supplied during laser processing can be suppressed. Although not particularly limited, the tensile speed of 30 m / min in the high-speed peel strength measurement is a measurement condition that corresponds well to a situation in which assist gas is sprayed on the adhesive sheet attached to the workpiece when the workpiece is processed with a short-wavelength laser beam, for example. When the adhesive sheet is lifted by the assist gas supplied during laser processing (typically, partial peeling occurs due to the assist gas entering the adhesive interface between the workpiece and the adhesive sheet due to the wind pressure from the cut portion by the laser light), the adhesive sheet is exposed to heat in a state where the adhesive sheet is released from the fixation (bonding by the adhesive) to the workpiece, and the thermal contraction increases, which may cause inconvenience such as the surface of the workpiece being easily exposed on both sides of the cut portion. An adhesive sheet having a high-speed peel strength of 3.0 N / 10 mm or more can effectively suppress lifting of the adhesive sheet during cutting. In some preferred embodiments, the high-speed peel strength of the adhesive sheet is 3.5 N / 10 mm or more, more preferably 4.0 N / 10 mm or more, even more preferably 4.5 N / 10 mm or more, even more preferably 5.0 N / 10 mm or more, even more preferably 5.5 N / 10 mm or more, and particularly preferably 6.0 N / 10 mm or more.

[0129] Although not particularly limited, the upper limit of the high-speed peel strength can be, for example, about 15N / 10mm or less, and may be about 12N / 10mm or less. By limiting the high-speed peel strength, a removable adhesive sheet can be obtained. From the viewpoint of obtaining good removable properties, in some preferred embodiments, the high-speed peel strength is 10N / 10mm or less, may be 9.0N / 10mm or less, may be 8.0N / 10mm or less, or may be 7.0N / 10mm or less. By setting the high-speed peel strength to a predetermined value or less within the above range, the work load when peeling the adhesive sheet from the adherend is reduced, and peeling defects such as the adhesive sheet being torn during peeling can be prevented.

[0130] (low speed peel strength) Although not particularly limited, the adhesive sheet preferably has a low-speed peel strength of 3.0 N / 10 mm or less, measured at a tensile speed of 0.3 m / min one week after being attached to a stainless steel (SUS) plate under an environment of 23° C. and 50% RH. An adhesive sheet having the above low-speed peel strength can have good removability. In some preferred embodiments, the low-speed peel strength may be 2.5 N / 10 mm or less, 2.0 N / 10 mm or less, or 1.5 N / 10 mm or less. By making the low-speed peel strength a predetermined value or less, for example, the effort required to peel off an adhesive sheet that has been attached to an adherend and is no longer needed thereafter can be reduced, improving workability. In addition, suppressing the low-speed peel strength is also meaningful from the viewpoint of preventing adhesive residue from being left on the surface of the adherend after the adhesive sheet is peeled off.

[0131] In addition, the low-speed peel strength of the adhesive sheet is preferably 0.5 N / 10 mm or more. An adhesive sheet with high low-speed peel strength adheres well to an adherend and is less likely to peel off. For example, when the adhesive sheet is used for surface protection during processing such as laser processing, peeling of the adhesive sheet during processing steps such as bending and drilling (these may be post-laser processing) tends to be effectively suppressed. From the viewpoint of obtaining a higher effect, in some preferred embodiments, the low-speed peel strength of the adhesive sheet is, for example, 1.0 N / 10 mm or more, may be 1.5 N / 10 mm or more, or may be 2.0 N / 10 mm or more.

[0132] More specifically, the high-speed peel strength and the low-speed peel strength are measured by the method described in the Examples below.

[0133] (Laser light absorption characteristics) Although not particularly limited, in an embodiment in which the adhesive sheet is used for laser processing, the adhesive sheet preferably has a laser light absorptance in the wavelength range of the laser light used for processing (typically, the laser light absorptance at the main wavelength of the laser light) of 20% or more. This laser light absorptance means the proportion of the laser light actually absorbed by the adhesive sheet out of the laser light irradiated to the adhesive sheet. According to an adhesive sheet having a laser light absorptance of 20% or more, the laser light can be efficiently absorbed. In some embodiments, the laser light absorptance of the adhesive sheet may be, for example, 25% or more, 30% or more, 45% or more, 60% or more, or 75% or more. The laser light absorptance of the adhesive sheet may be 100%, but in practical terms, it is preferably 95% or less, and may be 90% or less.

[0134] In this specification, the term "laser light absorptance" refers to a value calculated from the transmittance T (%) and reflectance R (%) of a sample measured using a spectrophotometer (e.g., a spectrophotometer manufactured by Hitachi High-Technologies Corporation, model "U-4100" or an equivalent product) using the following formula (I). Absorption rate A(%)=100(%)-T(%)-R(%) (I)

[0135] In this specification, for example, "laser light absorptance in the wavelength range of 900 nm to 1100 nm" refers to the minimum laser light absorptance in that wavelength range. Furthermore, unless otherwise specified, the laser light absorptance in this specification refers to the laser light absorptance of the back surface of the adhesive sheet or substrate (the surface on the side irradiated with the laser light, i.e., the surface opposite to the surface attached to the workpiece).

[0136] The transmittance and reflectance of the adhesive sheet are not particularly limited. In some embodiments, the adhesive sheet may have a laser light transmittance of less than 70% at a wavelength where the laser light absorptance is the minimum within the wavelength range of the laser light used for processing, for example, less than 50%. In some embodiments, the adhesive sheet may have a laser light reflectance of less than 50% at a wavelength where the laser light absorptance is the minimum, for example, less than 40%, less than 20%, or less than 10%. An adhesive sheet that satisfies at least one of the transmittance and the reflectance (preferably both) is likely to have the preferred laser light absorptance disclosed herein.

[0137] <Application> The use of the adhesive sheet disclosed herein is not particularly limited. The adhesive sheet disclosed herein can be used for various applications by taking advantage of the feature that it can achieve both good high-speed peel strength, good adhesive residue prevention, and adherend contamination prevention. For example, it can be suitably used as a surface protective material (which can also be understood as a surface protective adhesive sheet). The surface protective material is attached to the surface of the adherend, and after achieving its protective purpose, it is peeled off from the adherend. It is particularly preferable to apply an adhesive sheet that can be peeled off without leaving any adhesive residue and without contaminating the adherend when peeled off again from the adherend. The adhesive sheet disclosed herein can be used for applications such as attaching to the surface of components such as metal plates, painted plates, aluminum sashes, resin plates, decorative steel plates, vinyl chloride laminated steel plates, glass plates, optical films for liquid crystal such as polarizing films, optical components such as liquid crystal panels, electronic components, etc., when transporting, processing, or curing these components. The adhesive sheet disclosed herein is also suitable as a packaging adhesive sheet. Pressure-sensitive adhesive sheets used for packaging with packaging materials such as fibers, paper, boxes, etc. are required to have a peel strength that does not peel off when peeled at a certain high speed, and may also be required to be removed smoothly without leaving any adhesive residue when the package is opened. The pressure-sensitive adhesive sheets disclosed herein can be preferably used for such applications.

[0138] The adhesive sheet disclosed herein can be preferably used as one aspect of surface protection in a state where it is attached to a workpiece to be processed by various lasers and is laser cut in association with the laser processing of the workpiece. The laser light used in the above-mentioned laser processing is not particularly limited, and various conventionally known lasers can be adopted. For example, excimer lasers such as ArF excimer laser, KrF excimer laser, and XeCl excimer laser, solid-state lasers such as YAG laser, YLF laser, YVO4 laser, and titanium sapphire laser, semiconductor laser (sometimes called diode laser), fiber laser, carbon dioxide laser, etc. can be used. The type of laser processing performed on the workpiece with the adhesive sheet disclosed herein attached is not particularly limited, and can be, for example, cutting, drilling, cutting, engraving, etc.

[0139] The material of the workpiece is not particularly limited as long as it can be cut by laser light (for example, laser light of a carbon dioxide gas laser or a fiber laser), and may be, for example, metal or semimetal materials such as iron, iron alloys (carbon steel, stainless steel, chromium steel, nickel steel, etc.), aluminum, aluminum alloys, nickel, tungsten, copper, copper alloys, titanium, titanium alloys, silicon, etc.; resin materials such as polyolefin resins, polycarbonate resins, acrylic resins, etc.; ceramic materials such as alumina, silica, sapphire, silicon nitride, tantalum nitride, titanium carbide, silicon carbide, gallium nitride, gypsum, etc.; glass materials such as aluminosilicate glass, soda lime glass, soda aluminosilicate glass, quartz glass, etc.; cellulose-based materials such as paper, cardboard, wood, plywood, etc.; laminates or composites thereof; etc. Suitable examples of the workpiece include metal materials such as iron, aluminum, copper, titanium, and alloys (stainless steel, etc.) mainly composed of each of these metals. The shape of the workpiece is not particularly limited, and may be plate-shaped, cylindrical, block-shaped, etc. The adhesive sheet disclosed herein is preferable because it suppresses lateral slippage even when attached to a metal plate as a workpiece and then stacked.

[0140] The adhesive sheet disclosed herein can be preferably used in such laser processing in a state where it is attached to the surface of the workpiece on the laser light irradiation side. In addition, for the purpose of protecting the surface of the workpiece before and after laser processing or during laser processing, the adhesive sheet may be attached to the surface (back side) of the workpiece opposite to the laser light irradiation side. The adhesive sheet disclosed herein can be preferably used in such laser processing by a short-wavelength laser having a main wavelength of 900 to 1100 nm. As the short-wavelength laser, for example, a fiber laser having a main wavelength of about 1050 nm, a diode laser having a main wavelength of about 950 nm, etc. can be used.

[0141] The matters disclosed in this specification include the following. [1] A rubber latex containing 50% by weight or more of acid-modified synthetic rubber latex on a non-volatile basis; a rosin-based tackifier emulsion as a tackifier; Including, the acid-modified synthetic rubber contained in the acid-modified synthetic rubber latex has a glass transition temperature of −20° C. or lower; A pressure-sensitive adhesive composition, wherein the softening point of the rosin-based tackifier contained in the rosin-based tackifier emulsion is 140°C or lower. [2] The pressure-sensitive adhesive composition according to the above-mentioned [1], wherein the acid-modified synthetic rubber latex comprises an acid-modified styrene-butadiene copolymer latex. [3] The pressure-sensitive adhesive composition according to the above [1] or [2], wherein the content of the tackifier is 50 parts by weight or more and 100 parts by weight or less based on the non-volatile content, per 100 parts by weight of the rubber latex. [4] The pressure-sensitive adhesive composition according to any one of the above [1] to [3], which does not contain a crosslinking agent or contains the crosslinking agent in an amount of 5 parts by weight or less per 100 parts by weight of the rubber latex, based on the non-volatile content. [5] A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition according to any one of the above [1] to [4], and a substrate supporting the pressure-sensitive adhesive layer. [6] The pressure-sensitive adhesive sheet according to the above-mentioned [5], wherein an undercoat layer is disposed between the substrate and the pressure-sensitive adhesive layer. [7] The pressure-sensitive adhesive sheet according to [6] above, comprising a polyolefin resin film as the substrate. [8] The pressure-sensitive adhesive sheet according to the above [6] or [7], wherein the undercoat layer contains a polymer having an oxazoline group. [9] The pressure-sensitive adhesive sheet according to any one of the above [6] to [8], which is used for protecting the surface of an adherend.

[10] The pressure-sensitive adhesive sheet according to any one of the above [6] to [9], which is used by being cut with a laser beam having a dominant wavelength of 900 nm to 1100 nm. EXAMPLES

[0142] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those specific examples. In the following description, "parts" and "%" are by weight unless otherwise specified.

[0143] <Example 1> (Preparation of Pressure-Sensitive Adhesive Composition) To 100 parts of acid-modified SBR latex (manufactured by Zeon Corporation, trade name "Nipol LX432M", Tg -55°C, hereinafter sometimes referred to as "acid-modified SBR-A") based on non-volatile content, 70 parts of rosin ester emulsion (manufactured by KRATON Corporation, trade name "AQUATACK 6085", softening point 82°C, hereinafter sometimes referred to as "rosin-based Em-A") as a tackifier, 2 parts of an antioxidant (manufactured by Seiko Chemical Industry Co., Ltd., trade name "Nonflex CBP-E"), and 1 part of a water-soluble oxazoline-based crosslinking agent (manufactured by Nippon Shokubai Co., Ltd., trade name "Epocross WS-700") were added and mixed to prepare a water-dispersible pressure-sensitive adhesive composition according to this example.

[0144] (Preparation of resin film substrate) A support layer forming material consisting of 3 parts of a black master batch (hereinafter also referred to as Fe3O4 master batch) containing 40% Fe3O4 (iron tetraoxide powder with an average particle size of 250 nm) in polyolefin and 97 parts of LDPE (low-density polyethylene, manufactured by Tosoh Corporation, product name "Petrothene 186R") and a back layer forming material consisting of 94 parts of the support layer forming material and 6 parts of a silylated polyolefin master batch were co-extruded by inflation molding at a die temperature of 180°C to form a film, thereby obtaining a two-layered resin film consisting of a support layer and a back layer. The total thickness of this resin film was 80 μm, of which the thickness of the back layer was 8 μm. The silylated polyolefin master batch contains about 30% silylated polyolefin as a silicone-based release agent (prepared by the method shown in the example of JP 2011-26448 A) and about 70% PE resin, and the content of the silicone-based release agent in the back layer forming material is 1.8%. The resin film obtained in this way is referred to as PE in Table 1.

[0145] (Preparation of adhesive sheet) An oxazoline group-containing polymer emulsion (manufactured by Nippon Shokubai Co., Ltd., product name "Epocross K-2010E", Tg-50°C) was applied to the first surface (support layer side) of the resin film obtained above with a wire bar #3, and then dried to form an undercoat layer (application amount: 1.4 g / m2 based on non-volatile content). 2 ). The pressure-sensitive adhesive composition was applied to the surface of the undercoat layer of the resin film and dried to form a 12 μm thick pressure-sensitive adhesive layer. In this way, a pressure-sensitive adhesive sheet was obtained having a undercoat layer on a first surface of a resin film as a substrate, a pressure-sensitive adhesive layer on the undercoat layer, and a release surface on the second surface of the substrate.

[0146] <Examples 2-13> In preparing the adhesive composition, the type of rubber latex (natural rubber latex and acid-modified SBR latex) and weight ratio (based on non-volatile content), type of tackifier, amount of tackifier, type of crosslinking agent, and amount of crosslinking agent were changed as shown in Table 1. Except for this, the adhesive sheets of each example were obtained in the same manner as in Example 1. As the acid-modified SBR-B in Table 1, an acid-modified SBR latex (manufactured by DIC Corporation, product name "Luckstar 5215A", Tg -60°C) was used. As the natural rubber latex, a product name "HYTEX HA" (available from Nomura Trading Co., Ltd.) was used. As the rosin-based Em-B in Table 1, a rosin ester emulsion (product name "Hariestar SK-218NS", softening point 100°C) manufactured by Harima Chemicals was used. As the isocyanate-based crosslinking agent, a water-dispersible isocyanate-based crosslinking agent (manufactured by DIC Corporation, product name "Burnoc DNW-6000") was used. As the epoxy-based crosslinking agent, a water-soluble epoxy-based crosslinking agent (product name "Denacol EX-810") manufactured by Nagase ChemteX Corporation was used.

[0147] <Example 14> In the preparation of the adhesive sheet of Example 1, the first surface (the surface on the support layer side) of the resin film was subjected to a corona discharge treatment, and then the above adhesive composition was applied to the corona discharge treated surface and dried to form an adhesive layer having a thickness of 12 μm. The adhesive sheet of this example was obtained in the same manner as in Example 1.

[0148] <Example 15> An adhesive sheet of this example was obtained in the same manner as in Example 1, except that a 40 μm thick polypropylene film (manufactured by Futamura Chemical Co., Ltd., product name "FOA", indicated as "PP" in Table 1) was used as the substrate.

[0149] <Example 16> In the preparation of the pressure-sensitive adhesive composition of Example 1, an SBR latex (manufactured by Zeon Corporation, product name "Nipol LX110", Tg-47°C, not acid-modified) was used instead of the acid-modified SBR-A. Otherwise, a pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 1.

[0150] <Example 17> In the preparation of the pressure-sensitive adhesive composition of Example 1, an acid-modified SBR latex (manufactured by Zeon Corporation, product name "Nipol LX421", Tg-18°C, hereinafter sometimes referred to as "acid-modified SBR-C") was used instead of the acid-modified SBR-A. Otherwise, a pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 1.

[0151] <Example 18> In the preparation of the pressure-sensitive adhesive composition of Example 1, a petroleum-based tackifier emulsion was used as the tackifier instead of the rosin-based Em-A. Otherwise, the pressure-sensitive adhesive sheet of this example was obtained in the same manner as in Example 1. The petroleum-based tackifier emulsion used was prepared by the following method. That is, 100 parts of an aliphatic hydrocarbon resin (manufactured by ENEOS, product name "T-REZ RB100", softening point 100°C) was dissolved in 40 parts of toluene to obtain a resin solution. In addition, 4 parts of casein, 60 parts of water, and 28% ammonia water were mixed, and the casein was heated and dissolved at 70°C to obtain an aqueous ammonia solution of casein. The amount of 28% ammonia water used was 15 parts per 100 parts of casein. The aqueous ammonia solution of casein was cooled to 40°C, and 8 parts of ammonium salt of hydrogenated rosin (60% dihydroabietic acid) was added and mixed as an emulsifier to obtain an emulsifier-containing liquid. The emulsifier-containing liquid was then mixed with the resin solution and stirred at 800 rpm for 1 hour using a T·K Homo Disper manufactured by Tokushu Kika Kogyo Co., Ltd. to prepare a petroleum-based tackifier emulsion. The petroleum-based tackifier emulsion was prepared by adjusting the temperatures of the emulsifier-containing liquid and the resin solution to 40°C.

[0152] <Example 19> In the preparation of the adhesive composition of Example 1, a rosin ester emulsion manufactured by Arakawa Chemical Industries Co., Ltd. (product name "Tamanol E-200NT", softening point 150°C, hereinafter sometimes referred to as "rosin Em-C") was used as the tackifier instead of the rosin Em-A. Otherwise, an adhesive sheet according to this example was obtained in the same manner as in Example 1.

[0153] <Example 20> In the preparation of the pressure-sensitive adhesive composition of Example 1, natural rubber latex (available from Nomura Trading Co., Ltd., product name "HYTEX HA") was used instead of the acid-modified SBR-A. Otherwise, the pressure-sensitive adhesive sheet of this example was obtained in the same manner as in Example 1.

[0154] <Performance evaluation> A sample of an appropriate size was cut from the pressure-sensitive adhesive sheet prepared above, and the following items were evaluated. The results are shown in Table 1.

[0155] (1) Low-speed peel strength The pressure-sensitive adhesive sheet according to each example was cut into a rectangular shape with a width of 10 mm and a length of 100 mm to prepare a test piece. Under a standard environment of 23°C and 50% RH, the adhesive surface of the test piece was pressed against a stainless steel plate (SUS304BA plate) as an adherend by rolling a 2 kg rubber roller as specified in JIS Z0237:2000 back and forth once to obtain a measurement sample. same After leaving it under standard conditions for 1 week, the peel strength (low-speed peel strength) [N / 10 mm] was measured under the standard conditions at a tensile speed of 0.3 m / min and a peel angle of 180° using a universal tensile tester.

[0156] (2) High-speed peel strength The adhesive sheet according to each example was cut into a strip of 10 mm wide and 100 mm long to prepare a test piece. Under a standard environment of 23°C and 50% RH, the adhesive surface of the test piece was pressed against a stainless steel plate (SUS304BA plate) as an adherend by rolling a 2 kg rubber roller as specified in JIS Z0237:2000 back and forth once to obtain a measurement sample. After leaving the measurement sample under the same standard environment for one week, the peel strength (high-speed peel strength) [N / 10 mm] was measured under the standard environment using a universal tensile tester under the conditions of a tensile speed of 30 m / min and a peel angle of 180 degrees. If the high-speed peel strength is 3 N / 10 mm or more, it is determined that the high-speed peel strength is good.

[0157] In the measurement of each of the above peel strengths, a universal tensile compression tester (apparatus name "tensile compression tester, TCM-1kNB" manufactured by Minebea Co., Ltd.) was used as the tensile tester. The stainless steel plate (SUS304BA plate) used as the adherend was cleaned by the method specified in JIS Z0237:2000.

[0158] (3) Stain and adhesive residue evaluation The adherend surface after the high-speed peel test was photographed, the contrast was adjusted as necessary, and the image was binarized using image analysis software (ImageJ). After the adhesive sheet was peeled off, the percentage of the area (adhesive residue contamination area) of contamination (transfer of adhesive components) and adhesive residue (cohesive failure of adhesive) observed on the adherend was measured in an area of ​​10 mm x 10 cm, and evaluated according to the following criteria. A: Neither glue residue nor staining was observed (glue residue stained area 0%), or glue residue and staining were observed but the glue residue stained area ratio was 10% or less. B: Glue residue and staining were observed, and the percentage of the area stained with glue residue was more than 10% and less than 30%. C: Glue residue and staining were observed, and the percentage of the area stained with glue residue was more than 30% and less than 80%. D: Glue residue and staining were observed, and the percentage of the area stained with glue residue exceeded 80%. A or B was judged as a pass, and C or D was judged as a fail.

[0159] (3) Anchoring performance evaluation (3-1) Finger abrasion test The adhesive sheet according to each example was cut into a width of 20 mm and fixed to an acrylic plate so that the adhesive layer surface faced outward. A predetermined area (approximately 1 cm × 3 cm) on the adhesive layer surface was rubbed strongly with a finger at a constant force 50 times, and the number of rubs until the adhesive layer peeled off was recorded.

[0160] (3-2) Picking test The adhesive sheet according to each example was cut into a width of 20 mm, and the adhesive layer surfaces were bonded together with a hand roller. After one minute had passed, the bonded adhesive layers were peeled off with a certain force. This picking operation, which consisted of bonding and peeling, was repeated 10 times, and the number of picking operations until the adhesive layer peeled off was recorded.

[0161] (4) Mechanical stability evaluation The adhesive composition according to each example was adjusted to a non-volatile content of 40%, and the occurrence rate of aggregates was measured using a Marlon stability tester according to the following formula: Aggregate occurrence rate [%] = (aggregates / initial solid content) x 100 I asked for more. The conditions for the Marlon stability tester were a load of 10 kg, a rotation speed of 2000 rpm, and a shear time of 5 minutes. The sample with the occurrence rate of agglomerates of 0.5% or less was judged to be acceptable.

[0162] [Table 1]

[0163] As shown in Table 1, the adhesives according to Examples 1 to 15 were formed from adhesive compositions in which the rubber latex contained 50% by weight or more of an acid-modified synthetic rubber latex having a Tg of -20°C or less on a non-volatile basis, and further contained a rosin-based tackifier emulsion having a softening point of 140°C or less, and the adhesive sheets containing such adhesives had high-speed peel strengths of 3N / 10mm or more, and passed the staining and adhesive residue evaluations. The adhesive compositions according to the above examples also had good mechanical stability. On the other hand, Example 16, in which a synthetic rubber latex that was not acid-modified was used, Example 17, in which an acid-modified synthetic rubber having a Tg higher than -20°C was used, Example 18, in which a petroleum-based tackifier was used as the tackifier, and Example 19, in which the softening point of the rosin-based tackifier was higher than 140°C, all had low high-speed peel strengths and failed the staining and adhesive residue evaluations. Also, Example 20, in which natural rubber was used as the rubber latex, had poor mechanical stability. The above results show that an adhesive composition containing a rubber-based latex containing 50% by weight or more of acid-modified synthetic rubber latex on a non-volatile basis and a rosin-based tackifier emulsion as a tackifier, in which the glass transition temperature of the acid-modified synthetic rubber is -20°C or lower and the softening point of the rosin-based tackifier is 140°C or lower, can form an adhesive that has good mechanical stability, good high-speed peel strength, and excellent resistance to adhesive residue and contamination of the adherend, in a composition that uses rubber latex that is preferable in terms of eliminating organic solvents and being environmentally hygienic.

[0164] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0165] 1,2,3 Adhesive sheet 10 Base material 10A 1st side 10B 2nd side (back, peeling surface) 11 Back layer 12 Support layer 20 Adhesive layer 20A surface (adhesive surface) 30 Undercoat layer 30A (undercoat layer) surface

Claims

1. A rubber-based latex containing 50% by weight or more of acid-modified synthetic rubber latex on a non-volatile basis; a rosin-based tackifier emulsion as a tackifier; Including, the glass transition temperature of the acid-modified synthetic rubber contained in the acid-modified synthetic rubber latex is −20° C. or lower; The pressure-sensitive adhesive composition, wherein the rosin-based tackifier contained in the rosin-based tackifier emulsion has a softening point of 140° C. or lower.

2. The pressure-sensitive adhesive composition according to claim 1, wherein the acid-modified synthetic rubber latex comprises an acid-modified styrene-butadiene copolymer latex.

3. The pressure-sensitive adhesive composition according to claim 1 or 2, wherein the content of the tackifier is 50 parts by weight or more and 100 parts by weight or less based on non-volatile content, relative to 100 parts by weight of the rubber-based latex.

4. 3. The pressure-sensitive adhesive composition according to claim 1, which does not contain a crosslinking agent or contains the crosslinking agent in an amount of 5 parts by weight or less based on 100 parts by weight of the rubber latex on a non-volatile basis.

5. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition according to claim 1 or 2, and a substrate supporting the pressure-sensitive adhesive layer.

6. The pressure-sensitive adhesive sheet according to claim 5 , further comprising an undercoat layer disposed between the substrate and the pressure-sensitive adhesive layer.

7. The pressure-sensitive adhesive sheet according to claim 6 , comprising a polyolefin resin film as the substrate.

8. The pressure-sensitive adhesive sheet according to claim 6 , wherein the undercoat layer comprises a polymer having an oxazoline group.

9. The pressure-sensitive adhesive sheet according to claim 5 , which is used for protecting the surface of an adherend.

10. The pressure-sensitive adhesive sheet according to claim 5, which is used by being cut with a laser beam having a dominant wavelength of 900 nm to 1100 nm.

Citation Information

Patent Citations

  • Aqueous adhesive compositions, adhesive tapes, and wire harnesses

    JP4676945B2

  • adhesive film

    JP7058096B2